Ternary positive electrode plate for lithium battery, preparation method of the same, and lithium battery including the same
By integrating lithium-rich compounds and solid electrolytes into the positive electrode of lithium-ion batteries, the thermal stability and cycle life are enhanced, addressing safety concerns and maintaining high capacity and energy density.
Patent Information
- Application Number
- JP2024184091
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-05-27
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-05-26
Smart Images

Figure 2025013890000001_ABST
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority from Chinese patent application No. 202010464210.1, filed on May 27, 2020 with the Patent Office of the People's Republic of China and entitled "Territory positive plate for lithium batteries with high safety, high capacity and long cycle life, manufacturing method and use thereof," Chinese patent application No. 202010464212.0, filed on May 27, 2020 with the Patent Office of the People's Republic of China and entitled "Territory positive plate for lithium batteries with high safety and high capacity, manufacturing method and use thereof," and Chinese patent application No. 202010464214.X, filed on May 27, 2020 with the Patent Office of the People's Republic of China and entitled "Territory positive plate for lithium batteries with high safety and high capacity, manufacturing method and use thereof," the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to the field of battery materials, and to a positive electrode plate for lithium batteries having high safety and high capacity, and a method for producing and using the same. [Background technology]
[0003] In today's society, energy and the environment are the basic conditions for the survival and development of human society, the important material foundations for national construction and economic development, and two mutually contradictory challenges currently facing the whole world. In recent years, with the development of science, the rapid development of automobiles, energy depletion and environmental pollution have had a serious impact on the survival and development of society. New green energy technologies have been developed and utilized, and lithium-ion batteries have been widely used due to their advantages of long life, high operating voltage, high energy density, etc.
[0004] In the current social environment where energy crisis and environmental problems are becoming more and more prominent, new energy vehicles are gradually becoming the mainstream of the development of the automobile industry. The introduction and use of new energy vehicles can reduce the dependency on fossil fuels such as petroleum, and effectively reduce the emission of greenhouse gases and standard pollutants. As is well known, lithium ion batteries have been widely used in portable electronic products in recent years, and have begun to develop into power batteries and medium- and large-sized batteries, which not only poses great challenges to the cycle period, service life and manufacturing cost of lithium ion batteries, but also puts higher requirements on the safety of lithium ion batteries.
[0005] Lithium-ion batteries have the advantages of high energy density, good cycle performance, long service life, low self-discharge, no memory effect, etc., and are expected to be used in power batteries in the future. As a means of transportation, electric vehicles have attracted attention for their driving range and safety performance, but these mainly depend on the energy density, cycle life, output density, safety, etc. of the power battery.
[0006] In terms of the energy density of power batteries and the driving distance of electric vehicles, ternary materials containing nickel (Ni) have obvious advantages, and in particular, high-nickel ternary nickel-cobalt-manganese oxide and nickel-cobalt-aluminate lithium materials are promising for the future of power batteries. Ternary materials have the advantages of large discharge capacity, long cycle life, good low-temperature performance, and abundant raw materials, and can simultaneously solve the problems of low capacity of lithium iron phosphate, high cost of lithium cobalt oxide materials, and low stability of lithium manganese oxide materials. They are considered to be one of the most potential positive electrode materials for power lithium batteries, so high-nickel ternary materials are promising for application in the field of electric vehicles. However, they have poor high-temperature stability and are prone to thermal runaway, and the higher the nickel content in the ternary materials, the worse the thermal stability. Improving the safety of ternary positive electrode materials is the key to the widespread application of high-energy-density ternary lithium batteries in the power battery field, and is also one of the important directions currently being researched.
[0007] Although ternary positive electrode materials have many advantages, they have poor high-temperature stability and are prone to thermal runaway, and the higher the nickel content in the ternary materials, the worse the thermal stability. Improving the safety of ternary positive electrode materials is the key to the widespread application of high-energy density ternary lithium batteries in the power battery field, and is also one of the important directions currently being researched.
[0008] Taking the ternary material lithium nickel manganese cobalt oxide as an example, the reasons for its poor safety are as follows:
[0009] 1) Lithium nickel manganese cobalt oxide has a low thermal decomposition temperature, high heat dissipation, and poor thermal stability. Compared with lithium iron phosphate, lithium nickel manganese cobalt oxide has a deoxidation temperature of 200°C and a heat dissipation of more than 800J / g, while lithium iron phosphate has a deoxidation temperature of 270°C and a heat dissipation energy of only 124J / g, and requires more than 400°C for large-scale decomposition.
[0010] 2) Lithium nickel manganese cobalt oxide is active and has strong oxidizing properties under high potential. It is also unstable and prone to generate oxygen, which will react with the electrolyte to generate side reactions, release large amounts of heat, and easily cause thermal runaway, which may reduce the cycle life and storage life of the ternary positive electrode material.
[0011] The above problems are the causes of the poor safety performance of ternary lithium batteries. How to effectively resolve the safety risks of ternary batteries and prevent the occurrence of thermal runaway in batteries has become an issue that enterprises at home and abroad in China must urgently resolve.
[0012] At present, the methods for improving the safety of lithium batteries mainly include coating of positive electrode material, electrolyte additives, PTC coating, insulating / flame retardant coating, coating on ceramic separator, modification of negative electrode material, etc. For example, CN103151513B, a high-performance ternary power battery and its manufacturing method, discloses a lithium nickel cobalt manganese oxide ternary material coated with Al2O3 to improve the safety performance of the ternary battery, but this invention has low safety improvement at high temperatures and limited effect. CN104409681A, a manufacturing method for lithium ion battery plate including PTC coating, discloses that the safety of lithium ion batteries is improved by coating a current collector with a temperature-sensitive precoat that has good conductivity at room temperature and a rapid increase in electrical resistance when the temperature rises, preventing further temperature rise of the battery, and then coating the positive electrode active material or the negative electrode active material. However, because the thermal runaway caused by needle punching occurs instantaneously, the mechanism of action of this coating is not up to the task, and it cannot effectively enhance the safety of the needle punching. In addition, the above-mentioned methods such as coating the positive electrode material, painting the ceramic separator, using electrolyte additives, constructing PTC coatings, and constructing insulating and flame-retardant coatings reduce the electrochemical performance of the positive electrode, and it is necessary to optimize the overall performance of the positive electrode material modified by these methods, while it also has a certain impact on the manufacturing process of the electrode and the battery core, making it difficult to mass-produce. In addition, the above-mentioned methods such as coating the positive electrode material, painting the ceramic separator, using electrolyte additives, constructing PTC coatings, and constructing insulating and flame-retardant coatings reduce the electrochemical performance of the positive electrode, and it is necessary to optimize the overall performance of the positive electrode material modified by these methods, while it also has a certain impact on the manufacturing process of the electrode and the battery core, making it difficult to mass-produce. CN107768647A discloses a highly safe coated high-nickel ternary positive plate, the positive plate including a positive electrode layer formed of a high-nickel ternary positive electrode material and a coating layer coated on the surface of the positive electrode layer, the coating layer containing 1% by mass to 95% by mass of an inorganic flame retardant and 1% by mass of an inorganic phase change material. % to 95% by mass of an inorganic flame retardant and 1% to 20% by mass of a highly thermally conductive inorganic material, the inorganic flame retardant is one or more selected from aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate, antimony oxide, zinc borate, and a molybdenum-containing inorganic compound, the inorganic phase change material is one or more of a mixture or complex formed with one or more selected from AlCl3, LiNO3, NaNO3, KNO3, and NaNO2, and a molten salt-based compound, the highly thermally conductive inorganic material is one or more selected from graphite, graphene, carbon nanotubes, and aluminum nitride, the high nickel ternary positive electrode material is selected from lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminate, and in this form, the problem of the stability of the high nickel material in a highly oxidized state cannot be fundamentally avoided.
[0013] Therefore, it is of great significance to develop a positive electrode plate for lithium batteries that has high safety and high capacity under extreme conditions such as overcharging, high temperature, needle punching, pressing, internal short circuit, external short circuit, thermal abuse and overheating. Summary of the Invention
[0014] The object of the present invention is to provide a positive electrode plate for a lithium battery, which is highly safe and has a high capacity, and which contains at least one lithium-rich compound selected from a lithium-rich manganese solid solution, a lithium-rich solid electrolyte, and delithiated silicon monoxide, and a manufacturing method and use thereof. The lithium-rich compound releases Li ions under extreme conditions such as battery overcharging, high temperature, needle punching, pressing, internal short circuit, external short circuit, thermal abuse, and overheating, and fills the lithium vacancies in the positive electrode material, thereby reducing the oxidation state of the positive electrode under extreme conditions, stabilizing the lattice structure of the positive electrode material, and improving the safety of the battery manufactured using this positive electrode material. Moreover, the positive electrode plate for a lithium battery has a high surface capacity while maintaining excellent cycle performance, so that the battery achieves high safety while maintaining high specific energy and good cycle life.
[0015] Here, the high safety means that the lithium-rich compound capable of releasing lithium ions even under extreme conditions such as overcharging, high temperature, needle punching, pressing, internal short circuit, external short circuit, thermal abuse, and overheating is contained in the positive electrode plate for lithium batteries, and thus the safety of the battery manufactured using the positive electrode plate is significantly improved, and the battery passes needle punch detection and hot box testing at 190°C, and no fire or explosion occurs during such processes.
[0016] Here, the high capacity means that the surface capacity of the positive electrode plate for the lithium battery is 4 mAh / cm 2 It means reaching more than that.
[0017] In order to achieve the object of the present invention, the present invention adopts the following technical solutions:
[0018] In a first aspect, the present invention provides a positive electrode plate for a lithium battery, which comprises at least one lithium-rich compound selected from a lithium-rich manganese-based solid solution, a lithium-rich solid electrolyte, and lithium-free silicon monoxide.
[0019] The lithium-rich compound of the present invention releases Li ions under extreme conditions such as overcharging, high temperature, needle punching, pressing, internal short circuit, external short circuit, thermal abuse, and overheating of the battery, and fills lithium vacancies in the positive electrode material, thereby stabilizing the lattice structure of the positive electrode material and improving the safety of the battery manufactured using this positive electrode material. Moreover, the positive electrode plate for lithium batteries can maintain excellent cycle performance while having a high areal capacity.
[0020] Conventional high-nickel ternary positive plates are highly oxidizable under extreme conditions and have low transition metal content. The dissolution of the material makes the material structure unstable, causing the positive electrode material to generate oxygen, which then undergoes a side reaction with the electrolyte, releasing large amounts of heat and making it susceptible to thermal runaway, posing a safety hazard.
[0021] The positive electrode plate of the present invention is compounded with a lithium-rich compound, which can stabilize the lithium content in the positive electrode, improve the thermal stability of the entire positive electrode, and improve the safety performance of the battery under extreme conditions of the battery.
[0022] Preferably, the lithium-rich compound can release lithium ions under extreme conditions of the battery.
[0023] Preferably, the extreme conditions of the battery include at least one of battery overcharge, high temperature, needle punching, pressing, internal short circuit, external short circuit, thermal abuse, and overheating.
[0024] Preferably, the molecular formula of the lithium-rich manganese-based solid solution as the lithium-rich compound is xLi2MnO3·(1-x)LiMO2 (where 0 < x ≤ 1, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9, etc., preferably 0.9 to 1.0, and M is at least one selected from Ni, Co, or Mn).
[0025] Here, the lithium-rich manganese-based solid solution as the lithium-rich compound is different from the conventional positive electrode material and is a solid solution of two phases (Li2MnO3 and LiNi x Co y Mn 1-x-y O2).
[0026] Preferably, the lithium-rich solid electrolyte is selected from solid electrolytes doped with Li7La3Zr2O 12 and Li7La3Zr2O 12 and the doping element is at least one of La, Nb, Sb, Ga, Te, W, Al, Sn, Ca, Ti, Hf, Ta.
[0027] Preferably, the molecular formula of the silicon monoxide in the delithiated state is Li x SiO y(In the formula, x is 1.4 to 2.1, for example, 1.5, 1.6, 1.7, 1.8, 1.9, or 2, and y is 0.9 to 1.1, for example, 0.92, 0.95, 0.98, 1, 1.02, or 1.08.)
[0028] In the molecular formula of the lithium-free silicon monoxide of the present invention, x is 1.4 to 2.1, and y is 0.9 to 1.1. When the above composition is used, the battery can timely release lithium ions under extreme conditions such as overcharging, high temperature, needle punching, pressing, internal short circuit, external short circuit, thermal abuse, and overheating, maintain the balance of lithium ions in the positive electrode, improve the thermal stability of the positive electrode, and provide the battery with high safety even under extreme conditions.
[0029] Preferably, the particle diameter D50 of the lithium-rich compound particles is 0.1 to 10 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or 9 μm, and preferably 0.5 to 2 μm.
[0030] Here, the particle size of the lithium-rich compound particles is limited to 0.1-10 μm, which is advantageous for the battery to release lithium ions under extreme conditions, maintain the lithium content in the positive electrode, and improve safety. If the particle size of the particles is <0.1 μm, the interface resistance becomes large, which affects the ion transport in the positive electrode plate. If the particle size of the particles is >10 μm, the barrier effect on the positive electrode active particles is insufficient, and as a result, the improvement of the safety performance of the battery is insufficient.
[0031] Preferably, the total mass of the positive electrode active material and the lithium-rich compound in the positive electrode plate for a lithium battery is The content of the lithium-rich compound is 0.1 to 20 mass%, for example, 0.5 mass%, 1 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass%, 7 mass%, 9 mass%, 10 mass%, 12 mass%, 14 mass%, 16 mass%, or 18 mass%, and preferably 1 to 5%, relative to 100%.
[0032] When the amount of the lithium-rich compound of the present invention is within the above range, the battery can maintain the lithium content in the positive electrode under extreme conditions and can achieve the effect of improving safety. When the amount of the lithium-rich compound is ≦0.1% by mass, the amount of Li provided is limited, and the effect of improving the safety performance of the high-energy battery is insufficient. When the amount of the lithium-rich compound is ≧20% by mass, the content of the positive electrode active material is reduced, resulting in a decrease in the energy density of the battery.
[0033] Preferably, the surface capacity of the positive electrode plate for a lithium battery is 4 mAh / cm 2 More than 5mAh / cm 2 , 6mAh / cm 2 , 7mAh / cm 2 , 8mAh / cm 2 , 9mAh / cm 2 or 10mAh / cm 2 And so on.
[0034] By incorporating a lithium-rich compound into the positive electrode plate of the present invention, the cycle performance at high area capacity of the positive electrode plate is obviously improved.
[0035] Preferably, the positive electrode active material in the positive electrode plate for the lithium battery is LiNi x Co 1-x-y M y O2 (wherein x≧0.8, for example, 0.8, 0.83, 0.85, 0.88, or 0.90, y≦0.2, for example, 0.05, 0.08, 0.1, 0.13, 0.15, 0.18, or 0.2, and M is any one or a combination of at least two selected from Mn, Al, and Mg, and the combinations include, for example, a combination of Mn and Al, a combination of Mg and Mn, or a combination of Al and Mg).
[0036] In a second aspect, the present invention provides a method for producing a cathode using a lithium-rich compound, the method comprising the steps of: premixing a cathode active material and a lithium-rich compound to obtain a premixed powder; mixing the premixed powder, a binder liquid, and a conductive agent to obtain a positive electrode slurry; and applying the positive electrode slurry onto a current collector, baking, cold pressing, and forming into a sheet to obtain the positive electrode plate for a lithium battery according to the first aspect.
[0037] Preferably, the premixed powder, binder liquid, and conductive agent are mixed in such a manner that the binder liquid is added to the premixed powder, and then the conductive agent is added to obtain the positive electrode slurry.
[0038] In a third aspect, the present invention provides a battery comprising the positive electrode plate for a lithium battery according to the first aspect.
[0039] Preferably, the battery further comprises a negative plate, and the negative active material in the negative plate is selected from silicon monoxide and / or silicon carbon.
[0040] Preferably, the negative electrode plate includes a negative electrode active material, a conductive agent, a thickener, and a binder.
[0041] Preferably, the battery further comprises a separator.
[0042] Preferably, the separator is selected from separators having a ceramic coating.
[0043] Preferably, the thickness of the separator is 10 to 40 μm, for example, 12 μm, 15 μm, 1 The particle size is, for example, 8 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, or 38 μm, and the porosity is 20 to 60%, for example, 25%, 30%, 35%, 40%, 45%, 50%, or 55%.
[0044] Preferably, the battery further comprises an electrolyte solution comprising a lithium salt, a solvent and a film-forming additive.
[0045] Preferably, the lithium salt is any one or a combination of at least two selected from LiPF6, LiBF4, and LiClO4, and examples of the combination include a combination of LiPF6 and LiBF4, a combination of LiClO4 and LiPF6, or a combination of LiBF4 and LiClO4.
[0046] Preferably, the solvent is at least one selected from ethylene carbonate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, and fluoroethylene carbonate.
[0047] Preferably, said film-forming additive is selected from VC and / or PS.
[0048] Another object of the present invention is to provide a ternary positive plate for a lithium battery, which has high safety and high capacity, comprising a current collector and a positive active material layer located on the surface of the current collector, the positive active material layer comprising an oxide solid electrolyte capable of transporting lithium ions, the oxide solid electrolyte being porous spherical particles, and a manufacturing method and use thereof. Since the porous spherical oxide solid electrolyte is dispersed in the positive active material layer of the ternary positive plate of the present invention, the safety of the lithium battery is significantly improved, and the lithium battery obtained by using this positive plate has a significantly improved pass rate in needle punch, heating and deformation pressing tests, and has a high specific capacity, with the specific capacity of the obtained lithium battery reaching 300Wh / kg or more.
[0049] Here, the high safety means that the lithium battery obtained by using the ternary positive electrode plate of the present invention passes a needle punch test, a test of heating at 180°C for 2 hours, and a 50% deformation pressing test; Here, the high capacity means that the surface capacity of the ternary positive electrode plate of the present invention is 4 mAh / cm 2 It means reaching more than that.
[0050] In order to achieve the object of the present invention, the present invention adopts the following technical solutions:
[0051] In a first aspect, the present invention provides a ternary positive electrode plate for a lithium battery having high safety and high capacity, comprising a current collector and a positive electrode active material layer located on a surface of the current collector, wherein the positive electrode active material layer comprises an oxide solid electrolyte capable of transporting lithium ions, and the oxide solid electrolyte is in the form of porous spherical particles.
[0052] Since the porous spherical oxide solid electrolyte is dispersed in the positive active material layer of the ternary positive plate of the present invention, the safety and capacity of the lithium battery obtained by the obtained ternary positive plate are significantly improved, and the obtained lithium battery passes the needle punch test, the 180°C heating test for 2 hours and the 50% deformation pressing test, and the energy density of the obtained lithium battery reaches 300Wh / Kg.
[0053] The lithium battery obtained by using the ternary positive plate of the present invention has better cycle performance under the condition of high areal capacity.
[0054] Preferably, the porosity of the porous spherical particles is 5 to 70%, for example 5%, 10%, 15%. , 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., preferably 40 to 70%.
[0055] The particle size of the oxide solid electrolyte is preferably 0.1 to 10 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 2 μm, 3 μm, etc., and is preferably 0.5 to 3 μm.
[0056] Since the particle size of the oxide solid electrolyte in the ternary positive electrode plate of the present invention is within the above range, when it is dispersed in the positive electrode active material layer, the safety and capacity of the lithium battery obtained by using the ternary positive electrode plate can be obviously improved. When the particle size of the oxide solid electrolyte is <0.1 μm, the particle size of the oxide solid electrolyte is too small, the interface resistance is large, ion transport is blocked, the interface impedance is increased, and the energy density of the battery is reduced. When the particle size of the oxide solid electrolyte is >10 μm, the particle size is too large, and the effect of blocking the contact between the positive electrode particles is insufficient, resulting in insufficient improvement in safety.
[0057] Preferably, the content of the oxide solid electrolyte is 0.1 to 10 mass%, for example, 0.5 mass%, 1 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass%, 6 mass%, 7 mass%, 8 mass%, or 9 mass%, and preferably 1 to 5 mass%, relative to the total mass of the positive electrode active material and the oxide solid electrolyte in the positive electrode active material layer being 100%.
[0058] The amount of oxide solid electrolyte added in the ternary positive electrode plate of the present invention within the above range is advantageous for improving the safety and capacity of the obtained lithium battery. If the content of oxide solid electrolyte is less than 0.1%, the amount of oxide solid electrolyte is too small, the heat absorption and heat insulation effects of the solid electrolyte are insufficient, and the improvement of safety is also insufficient. If the content of oxide solid electrolyte is more than 10%, the amount of oxide solid electrolyte is too large, the proportion of positive electrode active material is reduced, and the energy density of the battery is reduced.
[0059] Preferably, the oxide solid electrolyte includes at least one of a NASICON structure, a perovskite structure, an anti-perovskite structure, a LISICON structure, and a garnet structure.
[0060] Preferably, the NASICON structure is Li 1+x Al x Ge 2-x (PO4)3(LAGP), Li 1+x Al x Ge 2-x The homocrystalline heteroatom doped compound of (PO4)3, Li1+y Al y Ti 2-y (PO4)3(LATP) and Li 1+y Al y Ti 2-y At least one selected from the heteroatom-doped compounds of the same crystal form of (PO4)3, preferably Li 1+y Al y Ti 2-y (PO4)3 (wherein, x is an integer of 0.1 to 0.4, such as 0.15, 0.2, 0.25, 0.3, or 0.35, and y is an integer of 0.1 to 0.4, such as 0.15, 0.2, 0.25, 0.3, or 0.35).
[0061] Preferably, the perovskite structure is Li 3z La 2 / 3-z TiO3(LLTO), Li 3z La 2 / 3-z The same crystalline heteroatom doped compound of TiO3, Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Hf 1 / 4 O3(LSTH), Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Hf 1 / 4 O3 homocrystalline heteroatom doped compound, Li 2a-b Sr 1-a Ta b Zr 1-b O3(LSTZ) and Li 2a-b Sr 1-a Ta b Zr 1-b At least one selected from the homocrystalline heteroatom-doped compounds of O3, wherein z is 0.06-0.14, for example, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12 or 0.13, a is selected from 0.75×b, and b is 0.25-1, for example, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or 0.95.
[0062] Preferably, the anti-perovskite structure is Li 3-2x Mx HalO, Li 3-2x M x At least one selected from homocrystalline heteroatom-doped compounds of HalO, Li3OCl and homocrystalline heteroatom-doped compounds of Li3OCl, wherein Hal contains Cl and / or I, and M is Mg. 2+ , Ca 2+ , Sr 2+ Or Ba 2+ It is any one kind or a combination of at least two kinds selected from the above.
[0063] Preferably, the LISICON structure is Li 4-c S 1-c P c O4, Li 4-c S 1-c P c O4 isomorphic heteroatom doped compounds, Li 14 ZnGeO 16 (LZGO) and Li 14 ZnGeO 16 In the formula, c is 0 to 1, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9.
[0064] Preferably, the garnet structure is Li 7-d La3Zr 2-d O 12 (LLZO) and / or Li 7-d La3Zr 2-d O 12 In the formula, d is 0.1 to 0.6, for example, 0.2, 0.3 or 0.4.
[0065] Preferably, the area capacity of the ternary positive plate is 4 mAh / cm 2 More than 5mAh / cm 2 , 6mAh / cm 2 , 7mAh / cm 2 , 8mAh / cm 2 , 9mAh / cm 2 or 10mAh / cm 2And so on.
[0066] Preferably, the active cathode material in the active cathode layer is selected from high nickel ternary materials.
[0067] Preferably, the high nickel ternary material comprises lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminate.
[0068] Preferably, the molecular formula of the lithium nickel cobalt manganese oxide is LiNi x Co y Mn 1-x-y O2, and the molecular formula of the lithium nickel cobalt aluminate is LiNi x Co y Al 1-x-y O2, where x≧0.6, such as 0.65, 0.7, 0.8, 0.85 or 0.9.
[0069] In a second aspect, the present invention provides a method for producing a composition comprising the steps of: A step of premixing a positive electrode active material and an oxide solid electrolyte to obtain a premixed powder; adding a binder liquid and a conductive agent to the premixed powder and mixing them to obtain a positive electrode slurry; and applying the positive electrode slurry onto a current collector and drying the positive electrode slurry to obtain the positive electrode plate.
[0070] Preferably, the positive electrode active material is selected from high nickel ternary materials; Preferably, the mass ratio of the positive electrode active material to the oxide solid electrolyte is (90 to 99.9):(0.1 to 10), for example, 90:10, 92:8, 95:5, 98:2, 99:1, or 99.5:0.5.
[0071] Preferably, the premixing is performed in a ball mill or a stirrer, the revolution speed is 30-50 r / min, for example, 35 r / min, 40 r / min, or 45 r / min, and the dispersion rotation speed is 300 to 3000 r / min, for example, 500 r / min, 800 r / min, 1000 r / min, 1200 r / min, 1500 r / min, 1800 r / min, 2000 r / min, 2200 r / min, 2500 r / min, or 2800 r / min, and preferably, the dispersion rotation speed is 500 to 2000 r / min.
[0072] In a third aspect, the present invention provides a lithium battery comprising a ternary positive plate according to the first aspect. .
[0073] Preferably, the lithium battery includes any one of a liquid lithium battery, a semi-solid lithium battery, and an all-solid lithium battery.
[0074] Preferably, the liquid lithium battery comprises a ternary positive plate according to the first aspect, a negative plate and a liquid electrolyte.
[0075] Preferably, the semi-solid lithium battery comprises the ternary positive plate according to the first aspect, a negative plate and an electrolyte layer, the electrolyte layer containing a liquid electrolyte material.
[0076] Preferably, the solid state lithium battery comprises a ternary positive plate, a negative plate and a solid electrolyte layer according to the first embodiment.
[0077] Preferably, the solid electrolyte in the solid electrolyte layer is at least one selected from a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.
[0078] The object of the final aspect of the present invention is to provide a positive plate, a method for producing the same and a use thereof, in particular a ternary positive plate for a lithium battery having high safety, high capacity and long cycle life, a method for producing the same, a method for improving the safety of a lithium battery, a corresponding positive plate and a lithium battery.
[0079] In the "positive electrode plate having high safety, high capacity and long cycle life" of the present invention, the long cycle life means that the capacity retention rate of 1000 cycles, which is the 1C / 1C cycle life of a lithium battery manufactured using the positive electrode plate, reaches 80% or more, and the high capacity means that the surface capacity is ≧4mAh / cm 2 High safety means that the battery has passed the needle punch and 180°C hot box tests and has no fire, explosion or smoke in either the needle punch or 180°C hot box tests.
[0080] In order to achieve the above objectives, the present invention adopts the following technical solutions.
[0081] In a first aspect, the present invention provides a battery comprising a current collector and a cathode material layer located on a surface of the current collector, the cathode material layer comprising ternary cathode active material particles, a conductive agent, a binder, and oxide solid electrolyte particles capable of conducting lithium ions; The surface capacity of the positive plate is 4 mAh / cm 2 The present invention provides a ternary positive electrode plate for a lithium battery, in which the oxide solid electrolyte particles have a particle diameter D50 of 0.1 to 3 μm.
[0082] In the present invention, the surface capacity of the positive plate is 4 mAh / cm 2 More than 4mAh / cm 2 , 6mAh / cm 2 , 8mAh / cm 2 , 10mAh / cm 2 , 12mAh / cm 2 or 15mAh / cm 2 And so on.
[0083] In the positive electrode plate of the present invention, the ternary positive electrode active material particles function as the main active component, and in order to obtain a ternary positive electrode with high surface capacity, the prior art generally uses high nickel ternary positive electrode materials with high specific capacity or increases the thickness of the plate. On the one hand, the high temperature stability of the ternary positive electrode material is poor, and the higher the nickel content in the ternary positive electrode material, the worse the thermal stability; on the other hand, the thicker the electrode thickness, the longer the transport path of electrons and lithium ions, which increases the impedance of the battery and the Joule heat during the charge and discharge process. In the ternary positive electrode material with high surface capacity, the energy stored in the positive electrode material per unit area is high, and when a short circuit or overheating occurs, the energy that the positive electrode material can release per unit area is high, which poses a high safety risk. Therefore, a solution that combines high safety and high capacity is needed.
[0084] In the present invention, an oxide solid electrolyte having a particle diameter D50 of 0.1 to 3 μm is added to the positive electrode plate, and by combining it with a conductive agent and a binder, the surface capacity of the positive electrode plate is increased to 4 mAh / cm 2 The above positive plate improves the thermal stability of the positive plate and ensures the safety of the battery without affecting the high capacity and long cycle life. The technical principle is as follows: first, the oxide solid electrolyte particles have a certain ion transport ability, and can effectively prevent the contact between the ternary positive electrode active material particles, thereby improving the thermal stability while ensuring ion transport; second, the oxide solid electrolyte itself has a heat absorption effect, so it can absorb some heat and alleviate the overheating of the positive electrode; and further, the oxide solid electrolyte has high chemical stability, so it does not need to change the mainstream manufacturing process of the current positive plate, separator and battery, and has the advantages of high stability and low cost, which are suitable for large-scale application. Since the oxide solid electrolyte particles themselves have a certain ion conducting ability, within the range of the content of the solid electrolyte of the present invention, the introduction of the oxide solid electrolyte does not have any obvious adverse effect on the ion transport ability of the positive electrode. Furthermore, the endothermic effect of the oxide solid electrolyte reduces the average temperature of the positive electrode active material during charging and discharging, and reduces the side reactions of the ternary positive electrode active material at high temperatures, which is advantageous in ensuring a long cycle life of the battery.
[0085] In the present invention, the particle diameter D50 of the oxide solid electrolyte particles is 0.1 to 3 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 2.5 μm, or 3 μm. If the oxide solid electrolyte particle diameter is too small, the interface resistance increases obviously, ion transport is blocked, the positive electrode capacity decreases, and the energy density of the battery decreases. If the particle diameter is too large, the barrier effect against contact between the oxide solid electrolyte positive electrode particles is insufficient, and safety improvement is insufficient.
[0086] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. According to the following preferred technical solutions, the objectives and beneficial effects of the technology of the present invention can be further achieved.
[0087] Preferably, the particle diameter D50 of the oxide solid electrolyte particles is 0.5 to 2 μm.
[0088] Preferably, the content of the ternary positive electrode active material particles is 80 to 98% based on the total mass of the ternary positive electrode active material particles, the conductive agent, the binder and the oxide solid electrolyte particles being 100%; Preferably, the total mass of the ternary positive electrode active material particles, the conductive agent, the binder and the oxide solid electrolyte particles is 100%, and the content of the oxide solid electrolyte is 0.1 to 10%, for example, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 7.5%, 8%, 8.5%, 9% or 10%. If the content of the oxide solid electrolyte is less than 0.1%, the contact between the ternary positive electrode active material particles cannot be effectively barriered, and the improvement of safety is insufficient. If the content of the oxide solid electrolyte exceeds 10%, it affects ion transport, reduces lithium ion conductivity, affects the performance of the battery capacity, and reduces the energy density and cycle performance of the battery. Therefore, it is preferably in the above range, more preferably 1 to 5%.
[0089] Preferably, the content of the conductive agent is 0.1 to 8%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 3.5%, 4%, 5%, 6%, 7%, or 8%, relative to the total mass of the ternary positive electrode active material particles, the conductive agent, the binder, and the oxide solid electrolyte particles, which is 100%.
[0090] Preferably, the content of the binder is 0.1 to 10%, for example, 0.1%, 0.8%, 1.2%, 3%, 5%, 6%, 7%, 8%, or 10%, relative to the total mass of the ternary positive electrode active material particles, the conductive agent, the binder, and the oxide solid electrolyte particles, which is 100%.
[0091] Preferably, the oxide solid electrolyte particles are Li of NASICON structure. 1+x1 Al x1 Ge 2-x1 (PO4)3(LAGP) or its heteroatom-doped compounds, Li 1+x2 Al x2 Ti 2-x2 (PO4)3(LATP) or its isomorphic heteroatom-doped compounds, perovskite structure Li x 3La 2 / 3-x3 TiO3(LLTO) or its homocrystalline heteroatom doped compounds, Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Hf 1 / 4 O3(LSTH) or its isomorphic heteroatom-doped compounds, Li 2x4-y1 Sr 1-x4 Ta y1 Zr 1-y1 LiO3(LSTZ) or its isomorphic heteroatom-doped compounds with antiperovskite structure 3-2x5 M x5 HalO, Li3OCl or its heteroatom doped compounds, LISICON structure Li 4-x6 S 1-x6 P x6 O4 or its isomorphic heteroatom doped compounds, Li 14 ZnGeO 16 (LZGO) or its isomorphic heteroatom-doped compounds, Li with garnet structure 7-x7 La3Zr2-x7 O 12 (LLZO) or its isomorphic heteroatom-doped compounds, <x1≦0.75、0<x2≦0.5、0.06≦x3≦0.14、0.25≦y1≦1、x4=0.75y1、0≦x5≦0.01、0.5≦x6≦0.6;0≦x7<1であり、Mは、Mg 2+ , Ca 2+ , Sr 2+ Or Ba 2+ Other highly charged cations commonly used in the art are also applicable to the present invention, including, but not limited to, any one or a combination of at least two of the following:
[0092] Preferably, the oxide solid electrolyte particles are Li 1+x2 Al x2 Ti 2-x2 (PO4)3 and / or Li 7-x7 La3Zr 2-x7 O 12 and preferably Li 1+x2 Al x2 Ti 2-x2 (PO4)3.
[0093] The ternary positive electrode active material particles include lithium nickel cobalt manganese oxide (NCM) and / or lithium nickel cobalt aluminate (NCA).
[0094] Preferably, the chemical composition of the ternary positive electrode active material particles is LiNi x Co y M 1-x-y O2 (M is at least one of Mn or Al, and x≧0.6, for example, 0.6, 0.65, 0.7, 0.8 or 0.88). The ternary positive electrode active material according to the preferred technical solution is a high-nickel ternary positive electrode material, which has high specific energy but poor thermal stability. In the present invention, the ternary positive electrode active material is modified by using an oxide solid electrolyte in combination with a conductive agent and a binder, which can solve the safety problem and fully exert the advantage of high energy density.
[0095] Preferably, the conductive agent comprises a combination of one or at least two of Super-P, KS-6, carbon black, carbon nanofiber, CNT, acetylene black, or graphene. Representative non-limiting examples of the combination include a combination of Super-P and KS-6, a combination of Super-P and carbon black, a combination of Super-P and carbon nanofiber, a combination of carbon black and CNT, a combination of KS-6, carbon black, and CNT, etc., and preferably a combination of carbon nanotube and Super-P.
[0096] Preferably, the binder comprises one or a combination of at least two of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropene (PVDF-HFP), polyethylene oxide (PEO), or polytetrafluoroethylene (PTFE). Representative ranges of the combinations include, but are not limited to, a combination of PVDF and PEO, a combination of PVDF and PTFE, and a combination of PVDF and PVDF-HFP.
[0097] Preferably, the ratio of the particle size D50 of the ternary positive electrode active material particles to the particle size D50 of the oxide solid electrolyte particles is 5 or more, for example, 5, 6, 8, 10, 12, 13 or 15. If both particle sizes are close to each other, due to the limitation by the content of the solid electrolyte, under this particle size condition, the content of the solid electrolyte is insufficient to provide a barrier to the contact between the ternary positive electrode active material particles, resulting in poor safety of the material.
[0098] In a second aspect, the present invention provides a method for producing ... semiconductor device comprising the steps of: Step S1 of premixing positive electrode active material particles including ternary positive electrode active material particles and oxide solid electrolyte particles to obtain a premixed material; Step S2 of adding a binder liquid to the premixed material and mixing to obtain a primary slurry; Step S3 of adding and mixing a conductive agent to the primary slurry to obtain a secondary slurry; The surface capacity of the plate is 4mAh / cm 2 and Step S4 of applying the secondary slurry onto a current collector so as to obtain a positive plate, followed by baking and roll pressing.
[0099] In the method of the present invention, in steps S2 and S3, the ingredients may be added independently all at once or in stages.
[0100] Preferably, the premixing is vacuum premixing or premixing performed under the condition of a dew point ≦-30°C (such as -30°C, -35°C, -40°C, -45°C, or -50°C). In this preferred technical solution, the positive electrode active material particles and the oxide solid electrolyte particles are first premixed under the condition of vacuum premixing or dew point ≦-30°C, the purpose of which is to uniformly disperse both and ensure the stability of the ternary positive electrode active material and the oxide solid electrolyte. For example, under the condition of a dew point ≧0°C, Li 7-x7 La3Zr 2-x7 O 12 (0≦x7<1) is prone to side reactions with water, resulting in destruction of the product structure and deterioration of performance.
[0101] Preferably, the premixing and mixing is carried out in a ball mill or a stirrer.
[0102] Preferably, the premixing and mixing are carried out using a planetary centrifugal mixer, the revolution speed being 20 rpm or more, for example, 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 85 rpm, or 100 rpm, and independently preferably 30 to 90 rpm, and the rotation speed being 200 rpm or more, for example, 200 rpm, 300 rpm, 400 rpm, 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1300 rpm, 1500 rpm, 1750 rpm, 2000 rpm, 2200 rpm, 2500 rpm, or 3000 rpm, and independently preferably 500 to 2000 rpm.
[0103] Preferably, the premixing time is 0.5-4h, such as 0.5h, 1h, 1.5h, 2h, 3h or 4h, preferably 1-2h.
[0104] Preferably, the dew point is −45° C. or less, more preferably −60° C. or less.
[0105] The above revolution speed, rotation speed and dew point conditions are preferred in order to ensure good dispersion and structural stability of the oxide solid electrolyte, to provide a barrier to contact between the ternary positive electrode active material particles, and to improve the thermal stability of the positive electrode plate.
[0106] In a further preferred technical solution of the method of the present invention, the method comprises: Step S1: premixing the ternary positive electrode active material particles and the oxide solid electrolyte particles in a rotation / revolution mixer at a revolution speed of 30 to 90 rpm and a rotation speed of 500 to 2000 rpm for 0.5 to 4 hours to obtain a uniformly mixed premixed material; Step S2 of gradually adding a uniformly mixed binder liquid to the uniformly mixed pre-mixed material of step S1, setting the revolution speed to 30 to 90 rpm and the rotation speed to 500 to 2000 rpm to obtain a uniformly mixed slurry; Step S3 of gradually adding a conductive agent to the uniformly mixed slurry of step S2, setting the revolution speed to 30 to 90 rpm and the rotation speed to 500 to 2000 rpm, and finally obtaining a uniformly mixed ternary positive electrode slurry; The surface capacity of the plate is 4mAh / cm 2 As described above, the method includes step S4 of applying the slurry of S3 onto a current collector, followed by baking, roll pressing, and die cutting to obtain a highly safe and high-capacity ternary positive electrode plate.
[0107] In a third aspect, the present invention relates to a method for manufacturing a positive electrode plate, the method comprising the steps of adding oxide solid electrolyte particles having a particle size D50 of 0.1 to 3 μm and dispersing them between positive electrode active material particles, and the surface capacity of the positive electrode plate is 4 mAh / cm 2 As described above, a method for improving the safety of a lithium battery is provided.
[0108] The present invention also provides a positive plate obtained by the method of the third aspect.
[0109] In a fourth aspect, the present invention provides a lithium battery comprising the positive plate according to the first aspect.
[0110] Preferably, the lithium battery comprises a liquid lithium battery or a semi-solid lithium battery.
[0111] Preferably, the liquid lithium battery comprises a positive plate according to the first embodiment, a negative plate, and a liquid electrolyte (also called electrolyte).
[0112] Preferably, the semi-solid lithium battery comprises a positive plate according to the first embodiment, a negative plate, and an electrolyte layer containing a liquid electrolyte.
[0113] Compared with the prior art, the present invention has the following beneficial effects: (1) The positive electrode plate for a lithium battery of the present invention contains a lithium ion-rich compound capable of releasing lithium ions even under extreme conditions of use. A battery incorporating the positive electrode plate releases Li ions under extreme conditions such as overcharging or overheating of the battery, and fills lithium vacancies in the positive electrode material, thereby stabilizing the lattice structure of the positive electrode material, improving the safety of a battery manufactured using this positive electrode material, maintaining the lithium balance in the positive electrode, improving the thermal stability of the entire positive electrode, and improving the safety of the battery under extreme conditions. (2) In the positive electrode plate for a lithium battery of the present invention, the lithium-rich compound is blended, so that the cycle performance in the case of a positive electrode plate with a high surface capacity can be improved. (3) In the present invention, by dispersing porous spherical particulate oxide solid electrolyte in the positive electrode active material layer of the ternary positive electrode plate, the safety of the obtained lithium battery is significantly improved, and the obtained lithium battery passes the needle punch test, the 180°C heating test for 2 hours, and the 50% deformation compression test. (4) The specific capacity of a lithium battery obtained by using the ternary positive electrode plate of the present invention reaches 300 Wh / kg or more. (5) In the present invention, an oxide solid electrolyte having a particle diameter D50 of 0.1 to 3 μm is added to the positive electrode plate, and is used in combination with a conductive agent and a binder, so that the surface capacity of the positive electrode plate is 4 mAh / cm 2 The above positive plate can significantly improve the safety performance of the battery while maintaining the high capacity of the plate and the long cycle life of the battery. The technical principle is as follows: first, the oxide solid electrolyte particles have a certain ion transport ability and can effectively prevent the contact between the ternary positive electrode active material particles, thereby improving the thermal stability of the positive electrode while ensuring ion transport; second, the oxide solid electrolyte itself has a certain heat capacity, so it can absorb part of the heat generated in the positive electrode and alleviate overheating of the positive electrode; furthermore, even if the oxide solid electrolyte is directly mixed into the positive electrode material, it does not affect the electrochemical properties of the positive electrode active particles themselves. On the other hand, when the method of modifying the positive electrode active particles by coating them with oxide electrolyte is used, the coating layer affects the transport of ions and electrons in the positive electrode active particles, which adversely affects the overall performance of the battery. Furthermore, since the oxide solid electrolyte has high chemical stability, it can be directly mixed with the positive electrode active material prior to the manufacture of the plate. The positive electrode plate provided by the present invention is compatible with the mainstream manufacturing process of conventional lithium ion battery positive electrode plates, does not affect the manufacturing process of the positive electrode and the battery core, has low mass production costs, and is suitable for large-scale application. The lithium battery assembled using the positive plate of the present invention has the characteristics of high capacity, high safety, and long cycle, and the battery passes the needle punch test smoothly. A preferred embodiment of the positive plate of the present invention has the above effects and realizes a high specific energy of the battery (generally, the mass specific energy of the battery is 260Wh / Kg or more). [Brief description of the drawings]
[0114] [Figure 1] 1 shows the test curves of cycle performance when the energy density of the 15 Ah batteries of Comparative Example 1 and Examples 1, 3, and 5 reaches 300 Wh / Kg at high surface capacity. [Diagram 2]FIG. 1 shows a needle punch test of a high-energy battery of Comparative Example 1 in which a high-nickel ternary positive electrode material is used, and FIG. 2 shows a needle punch test of a high-energy battery of Example 3 in which a high-nickel ternary positive electrode plate is compounded with lithium-rich solid electrolyte Li7La3Zr2O12. [Diagram 3] FIG. 2 is a structural schematic diagram of the ternary positive electrode plate of the present invention. [Figure 4] FIG. 2 is a structural schematic diagram of a lithium battery assembled using the ternary positive electrode plate of the present invention, where: 1-ternary positive electrode plate; 10-aluminum foil; 11-positive active material; 12-oxide solid electrolyte; 2-negative electrode plate; 20-copper foil; 21-negative active material; 3-solid, liquid or semi-solid electrolyte; where the liquid lithium ion battery further includes a separator. [Diagram 5] FIG. 1 is a schematic diagram of the internal structure of a positive electrode material layer in a ternary electrode plate containing the oxide solid electrolyte of the present invention, where 1-oxide solid electrolyte, 2-ternary positive electrode active material, 3-conductive agent. [Figure 6] 1 is an image of the battery after a needle punch test in Comparative Example 4. [Figure 7] 13 is an image of the battery of Example 38 after needle punch testing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0115] The technical solutions of the present invention will be described clearly and completely below with reference to the embodiments of the present invention, but obviously, the described embodiments are only a part of the embodiments of the present invention, and are not all of the embodiments. All other embodiments that a person skilled in the art can obtain based on the embodiments of the present invention without requiring creative efforts belong to the scope of the present invention.
[0116] The technical solutions of the present invention are further described below through specific embodiments. It is obvious to those skilled in the art that the above examples are only for facilitating understanding of the present invention, and cannot be construed as specifically limiting the present invention.
[0117] Comparative Example 1 In this Comparative Example 1, no lithium-rich compound was mixed into the positive electrode plate, and the positive electrode active material in the positive electrode plate was LiNi 0.83 Co 0.12 Mn 0.05 The positive electrode plate was manufactured by the following method. The positive electrode active material was O2(Ni83), the binder was PVDF, and the conductive agent was CNT. The mass ratio of the positive electrode active material, the binder, and the conductive agent was 95:2:3. The binder liquid was mixed uniformly with Ni83, and a conductive agent was added to prepare a positive electrode slurry, which was then coated on an aluminum foil to produce a positive electrode with an areal capacity of 5.4 mAh / cm 2 The positive electrode plate is obtained, baked, cold pressed, and formed into a sheet to produce a positive electrode plate. The matching negative electrode plate (active material SiC) is assembled with a ceramic separator with a thickness of 15 μm and a porosity of 50%, and then welded, hi-pot tested, packaged, baked, and then charged with LiPF6 as a lithium salt, ethylene carbonate, dimethyl carbonate, and fluorine as a solvent. The electrolyte is then injected into the battery, which is then packaged, formed, and capacity graded to create the battery.
[0118] Example 1 In this embodiment, the positive electrode plate contains a lithium-rich manganese-based solid solution, which is 0.5Li2MnO3·0.5LiMn 0.54 Ni 0.13 Co 0.13 The mass ratio of the positive electrode active material to the lithium-rich compound is 94:6, the particle diameter of the lithium-rich compound particles is 500 nm, the positive electrode active material in the positive electrode plate is Ni83, the binder is PVDF, and the conductive agent is CNT, and the manufacturing method thereof is as follows: The positive electrode active material and the lithium-rich compound nanoparticles are premixed for 1 hour at a revolution speed of 40 r / min and a dispersion rotation speed of 500 r / min to obtain a premixed powder. The binder liquid was added to the premixed material so that the mass ratio of premixed powder:binder:conductive agent was 95:2:3, and after uniform mixing, the conductive agent was added to prepare a positive electrode slurry, which was then applied onto an aluminum foil and had an areal capacity of 5.4 mAh / cm. 2 The positive electrode plate is obtained, baked, cold pressed, and formed into a sheet to produce a positive electrode plate. The matching negative electrode plate (active material SiC) is assembled with a ceramic separator with a thickness of 15 μm and a porosity of 50%, and then welded, hi-pot tested, and packaged. After baking, an electrolyte containing LiPF6 as the lithium salt, a mixed solvent of ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate as the solvent, and VC as an additive is injected. After the electrolyte is injected, the plate is packaged and undergoes formation and capacity grading processes to create the battery.
[0119] Example 2 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich manganese-based solid solution is 90:10, and the lithium-rich manganese-based solid solution is 0.37Li2MnO3·0.63LiNi 0.13 Co 0.13 Mn 0.54 The remaining parameters and conditions were the same as those in Example 1, except that the lithium-rich manganese-based solid solution was O2 and the particle size of the lithium-rich manganese-based solid solution was 2 μm.
[0120] Example 3 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich solid electrolyte is 99.5:0.5, the particle diameter of the lithium-rich solid electrolyte is 200 nm, and the lithium-rich solid electrolyte is Li7La3Zr2O 12 Other than that, the remaining parameters and conditions were the same as in Example 1.
[0121] Example 4 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich solid electrolyte is 92:8, the particle size of the lithium-rich solid electrolyte is 2 μm, and the lithium-rich solid electrolyte is Li 6.75 La3Zr 1.75 Ta0.25 O 12 Other than that, the remaining parameters and conditions were the same as in Example 1.
[0122] Example 5 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich compound in the delithiation state is 99.5:0.5, the particle size of the lithium-rich compound in the delithiation state is 200 nm, and the lithium-rich compound in the delithiation state is Li 1.4 SiO 0.9 Other than that, the remaining parameters and conditions were the same as in Example 1.
[0123] Example 6 In comparison with Example 1, in this example, the positive electrode active material is LiNi 0.8 Co 0.1 Al 0.1 O2, and the lithium-rich compound in the delithiated state is Li 2.1 The remaining parameters and conditions were the same as those in Example 1, except that the positive electrode active material was SiO, the mass ratio of the positive electrode active material to the lithium-free lithium-rich compound was 95:5, and the particle size of the lithium-free lithium-rich compound was 1 μm.
[0124] Example 7 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich solid electrolyte is 94:6, the particle diameter of the lithium-rich solid electrolyte is 500 nm, and the lithium-rich solid electrolyte is Li7La3Zr2O 12 Other than that, the remaining parameters and conditions were the same as in Example 1.
[0125] Example 8 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich compound in the delithiation state is 94:6, the particle diameter of the particles of the lithium-rich compound in the delithiation state is 500 nm, and the lithium-rich compound in the delithiation state is Li 1.4 SiO 0.9 Other than that, the remaining parameters and conditions were the same as in Example 1.
[0126] Example 9 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich manganese-based solid solution is 94:6, the particle size of the lithium-rich lithium-rich manganese-based solid solution is 10 μm, and the lithium-rich manganese-based solid solution is 0.5Li2MnO3·0.5LiMn 0.54 Ni 0.13 Co 0.13 Other than O2, the remaining parameters and conditions were the same as in Example 1.
[0127] Example 10 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich manganese-based solid solution is 94:6, the particle size of the lithium-rich lithium-rich manganese-based solid solution is 100 nm, and the lithium-rich manganese-based solid solution is 0.5Li2MnO3·0.5LiMn 0.54 Ni 0.13 Co 0.13 Other than O2, the remaining parameters and conditions were the same as in Example 1.
[0128] Example 11 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich manganese-based solid solution is 99:1, the particle size of the lithium-rich lithium-rich manganese-based solid solution is 500 nm, and the lithium-rich manganese-based solid solution is 0.5Li2MnO3·0.5LiMn 0.54 Ni 0.13 Co 0.13 Other than O2, the remaining parameters and conditions were the same as in Example 1.
[0129] Example 12 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich manganese-based solid solution is 95:5, the particle size of the lithium-rich lithium-rich manganese-based solid solution is 500 nm, and the lithium-rich manganese-based solid solution is 0.5Li2MnO3·0.5LiMn 0.54 Ni 0.13 Co 0.13 Other than O2, the remaining parameters and conditions were the same as in Example 1.
[0130] Example 13 Compared with Example 1, in this example, the mass ratio of the positive electrode active material to the lithium-rich compound in the delithiation state is 80:20, the particle diameter of the particles of the lithium-rich compound in the delithiation state is 500 nm, and the lithium-rich compound in the delithiation state is Li 1.6 SiO 1. 1, the remaining parameters and conditions were the same as in Example 1.
[0131] Example 14 Compared with Example 5, in this example, the mass ratio of the positive electrode active material to the lithium-rich compound in the delithiation state is 99.5:0.5, the particle diameter of the particles of the lithium-rich compound in the delithiation state is 200 nm, and the lithium-rich compound in the delithiation state is Li 2.1 Other than SiO, the remaining parameters and conditions are the same as in Example 5. The batteries assembled using the positive electrode plates obtained in Comparative Example 1 and Examples 1 to 14 were tested. 1. Cycle test: In the case of high capacity, the energy density of the 15 Ah battery of Comparative Example 1 and Examples 1, 3 and 5 reaches 300Wh / Kg. The cycle performance is tested. If the discharge capacity percentage of the battery exceeds 80%, the test continues; otherwise, the test is stopped. The test results are shown in FIG. 1. As can be seen from FIG. 1 above, the discharge capacity percentage of the high capacity battery exceeds 80% after 1000 cycles at 1C. Meanwhile, the addition of lithium-rich compound to the positive plate improves the cycle performance of the battery. 2. Needle punch test: The energy density of a 15Ah battery is 300Wh / Kg or more. The test conditions are a needle with a diameter of 3~8mm and a speed of 25~80mm / s. The needle penetrates the core of the battery vertically and is left inside the battery for 1 hour. If there is no fire or explosion, it is considered to be a pass; otherwise, it is considered to be a fail.
[0132] [Table 1]
[0133] As can be seen from Table 1 above, the battery with lithium-rich compound added to the positive electrode has an energy density of more than 300Wh / Kg, passes the needle punch test, and has no obvious change in surface temperature after needle punching. When the amount of addition is 20%, the decrease in the energy density of the battery is obvious, while the battery without lithium-rich compound added does not pass the needle punch test. 3. Thermal shock test: The energy density of the 15Ah battery is more than 300Wh / Kg. It is heated to 190℃ for 2 hours with a temperature increase rate of 5℃ / min, and kept at 190℃ for 2 hours. After observing for 1 hour, if there is no fire or explosion, it is considered to be a pass, otherwise it is considered to be a fail. The test results are shown in Table 2.
[0134] [Table 2]
[0135] As can be seen from Table 2 above, the battery with lithium-rich compound added to the positive electrode has an energy density of over 300Wh / Kg and can withstand thermal shock at 190°C for 2 hours. When the amount of lithium-rich compound added is 20%, the energy density of the battery is obviously reduced, while when no lithium-rich compound is added, the battery fails the 190°C thermal shock test. In the present invention, the lithium-rich compound is added to the high nickel ternary positive plate, which obviously improves the safety performance of the high energy density battery. The batteries of Comparative Example 1 and Examples 1, 3, and 5 all have an energy density of 300Wh / Kg. In Examples 1, 3, and 5, the batteries with various lithium-rich compounds added all pass the needle punch test, the change in the surface temperature of the battery is not obvious, and the battery passes the thermal shock test of keeping warm at 190°C for 2 hours. This is mainly because the lithium-rich compound releases Li ions under the extreme conditions and fills the lithium vacancies in the positive electrode material, thereby stabilizing the lattice structure of the positive electrode material, stabilizing the internal lithium content of the positive electrode, and reducing the oxidation state of the positive electrode under extreme conditions, thereby improving the safety of the battery manufactured using this positive electrode material under extreme conditions. By comparing Examples 9, 10 and 1, the influence of various particle sizes on the safety performance of the battery is explained. If the particle size of the material added to the positive electrode is too small or too large, it is difficult to obtain a good safety improvement effect. If the particle size of the lithium-rich compound is too small, the interface resistance increases and ion transport is blocked. If the particle size is too large, the barrier effect on the positive electrode is insufficient, and the safety improvement is insufficient. Comparing Examples 5 and 13, the effect of the amount of lithium-rich compound added on the battery safety performance was examined. The effects of adding too little are shown in Table 1, whereby the improvement in safety performance is insufficient, whereas adding too much improves safety performance but reduces the active material particles in the positive electrode plate, resulting in a decrease in the energy density of the battery. The energy density of the battery in Example 13 was reduced to 294Wh / Kg. As can be seen from the comparison of Examples 1, 7 and 8, when the blending amount is the same, the one blended with the lithium-rich solid electrolyte has better safety performance and the maximum temperature on the battery surface is the lowest in the needle punch test. A structural schematic diagram of the ternary positive plate of the present invention is shown in FIG. 3. As can be seen from FIG. 3, the ternary positive plate 1 includes a current collector 10, for example an aluminum foil, and a positive electrode active material layer located on the surface of the current collector, and the positive electrode active material layer includes a positive electrode active material 11 and an oxide solid electrolyte 12. A structural schematic diagram of a lithium battery assembled using the ternary positive plate of the present invention is shown in FIG. 4. As can be seen from FIG. 4, the lithium battery includes a ternary positive plate 1, a negative plate 2, and a solid, liquid or semi-solid electrolyte 3 interposed between the ternary positive plate 1 and the negative plate 2. The negative plate 2 includes a current collector 20 and a negative active material layer located on the surface of the current collector, and the negative active material layer includes a negative active material 21.
[0136] Comparative Example 2 In this Comparative Example 2, in the ternary positive electrode plate, the current collector is aluminum foil, and the positive electrode active material is Ni83(LiNi 0.83 Co 0.11 Mn 0.06 O2), and the oxide solid electrolyte is LATP (Li 1.4 Al 0.4Ti 1.6 The mass ratio of the positive electrode active material to the oxide solid electrolyte was 97:3, the particle diameter of the oxide solid electrolyte was 0.8 μm, and the surface capacity of the ternary positive electrode plate was 4 mAh / cm 2 The manufacturing method thereof is as follows. Ni83 and LATP nanoparticles are premixed for 0.5 h at a revolution speed of 40 r / min and a dispersion speed of 1500 r / min to obtain a premixed powder. The binder liquid is added to the premixed powder so that the mass ratio of premixed powder:binder (PVDF):conductive agent (CNT) is 95:2:3, and after uniform mixing, the conductive agent is added to prepare a positive electrode slurry. Next, the positive electrode slurry is applied onto an aluminum foil and baked, and then cold pressed and cut to obtain a ternary positive electrode plate. Negative plate manufacturing A negative electrode slurry was prepared so that the mass ratio of negative electrode powder:conductive agent (Sp):CMC:SBR was 95.8:1:1.2:2, and then the negative electrode slurry was applied onto a copper foil, baked, cold pressed, and cut to obtain a negative electrode plate. The negative electrode powder used was SL450A-SOC nano silicon carbon negative electrode material manufactured by ▲Liyang Tianmu Leading Battery Material Technology Co., Ltd. The matching negative electrode plate and ceramic separator (the coating layer of the base film PP is Al2O3) are assembled, welded, hi-pot tested, top sealed and side sealed, then baked and injected with electrolyte (electrolyte is EC+DEC+FEC+LiPF6), followed by complete sealing, formation and capacity grading processes to manufacture the lithium battery, after which the electrical performance and safety are tested. The test results are shown in Table 3.
[0137] [Table 3]
[0138] As can be seen from Table 3, in the present invention, the oxide solid electrolyte is added to the high nickel ternary positive plate, thereby improving the safety of the battery. The 15Ah battery achieves 300Wh / kg at 0.3C / 0.3C, and the discharge retention rate at 3C rate reaches more than 80%, and the overall safety of the battery is improved. It has passed needle punch, 180°C hot box and 50% pressing deformation tests. This is mainly because the oxide solid electrolyte is added to the ternary positive electrode active material to effectively prevent the contact between the ternary active particles and improve the thermal stability of the positive plate. In addition, the oxide solid electrolyte of the present invention itself has a certain heat capacity, so it can absorb part of the heat generated in the positive electrode and alleviate the overheating of the positive electrode, and also improve the safety performance of the battery.
[0139] Example 15 Compared with Comparative Example 2, in this Example 15, the oxide solid electrolyte was in the form of porous spheres, and the porosity was 50%, except that the rest of the parameters and conditions were the same as those of Comparative Example 2. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the results are shown in Table 4.
[0140] [Table 4]
[0141] As can be seen from Table 4, compared with Comparative Example 2, the oxide solid electrolyte mixed in the high-nickel ternary positive plate is porous and spherical, and the porous spherical solid electrolyte has more reaction sites, which improves the rate performance of the battery, makes the 3C rate discharge retention rate of the battery more than 90%, and also improves the energy density of the battery to 305Wh / kg. Moreover, when the porous spherical oxide solid electrolyte is mixed in the positive electrode, more heat generated in the positive electrode is absorbed, the thermal stability of the battery is more effectively improved, and the safety performance of the battery is further improved.
[0142] Example 16 Compared with Example 15, in this example, the mass ratio of the positive electrode active material to the oxide solid electrolyte was 95:5, and the rest of the parameters and conditions were the same as those in Example 15. The results of electrical performance and safety performance tests conducted on the lithium battery obtained in this example are shown in Table 5.
[0143] [Table 5]
[0144] As can be seen from Table 5, compared with Example 15, in this example, the content of solid electrolyte in the positive electrode is increased to 5%, and the safety performance is slightly improved, but the energy density of the battery is obviously reduced, and the 3C rate performance of the battery is also reduced from 90% to 83%, which is because with the increase in solid electrolyte, the proportion of active material in the positive electrode material is reduced, resulting in a decrease in the energy density of the battery and a deterioration in the rate performance of the battery.
[0145] Example 17 In comparison with Example 15, in this example, the oxide solid electrolyte was changed from LATP to LAGP (Li 1.5 Al 0.5 Ge 1.5 The remaining parameters and conditions were the same as in Example 15, except that (PO4)3) was changed. The results of electrical performance and safety performance tests performed on the lithium battery obtained in this example are shown in Table 6.
[0146] [Table 6]
[0147] As can be seen from Table 6, compared with Example 15, in this example, when the porous spherical solid electrolyte is changed from LATP to LAGP, the energy density of the battery is slightly decreased and the rate discharge performance is slightly decreased, because the conductivity of LAGP is slightly lower than that of LATP, which causes a slight decrease in the performance of the battery.
[0148] Example 18 Compared with Example 15, in this example, the dispersion rotation speed in premixing was 500 r / min, except that the rest of the parameters and conditions were the same as those in Example 15. The results of electrical performance and safety performance tests performed on the lithium battery obtained in this example are shown in Table 7.
[0149] [Table 7]
[0150] As can be seen from Table 7, compared with Example 15, the dispersion rotation speed in the premixing was changed from 1500 r / min to 500 r / min. With the decrease in the rotation speed, the oxide solid electrolyte can be uniformly dispersed, and the energy density and rate performance of the battery are hardly affected.
[0151] Example 19 Compared with Example 15, in this example, the particle size of the oxide solid electrolyte was 2 μm, except that the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0152] [Table 8]
[0153] As can be seen from Table 8, compared with Example 15, the particle size of the oxide solid electrolyte changed from 0.8 μm to 2 μm, and the particle size increased obviously; however, there was almost no change in the energy density and rate performance of the battery, and no obvious change in the needle punch performance.
[0154] Example 20 Compared with Example 15, in this example, the particle size of the oxide solid electrolyte was 0.5 μm, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0155] [Table 9]
[0156] As is clear from Table 9, compared with Example 15, in this Example, the particle size of the oxide solid electrolyte changed from 0.8 μm to 0.5 μm, and the particle size of the solid electrolyte became smaller, but there was almost no change in the energy density and rate performance of the battery, and the safety performance of the battery was almost unchanged.
[0157] Example 21 Compared with Example 15, in this example, the particle size of the oxide solid electrolyte was 3 μm, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0158] [Table 10]
[0159] As is clear from Table 10, compared with Example 15, in this Example, the particle size of the oxide solid electrolyte is changed from 0.8 μm to 3 μm, the energy density and rate performance of the battery are almost maintained, and no obvious deterioration in safety performance is observed.
[0160] Example 22 Compared with Example 15, in this example, the mass ratio of the positive electrode active material to the oxide solid electrolyte was 99.9:0.1, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0161] [Table 11]
[0162] As can be seen from Table 11, compared with Example 15, in this example, the content of solid electrolyte in the positive electrode material is reduced to 0.1%, and the remaining parameters remain unchanged. The energy density of the battery is obviously improved, and the rate performance is also improved. However, the safety performance of the battery does not pass the needle punch and 180°C hot box tests. This is because the content of oxide solid electrolyte is reduced, which cannot effectively prevent the contact between the ternary active particles, and cannot absorb part of the heat generated in the positive electrode, resulting in the deterioration of the safety performance of the battery.
[0163] Example 23 Compared with Example 15, in this example, the mass ratio of the positive electrode active material to the oxide solid electrolyte was 90:10, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0164] [Table 12]
[0165] As can be seen from Table 12, compared with Example 15, in this example, the content of solid electrolyte in the positive electrode material is increased to 10%, and the energy density of the battery is obviously reduced, the cycle number is deteriorated, and the rate performance is deteriorated, which is because the proportion of the positive electrode active material is reduced due to the high content of solid electrolyte, and as a result, the electrochemical performance of the battery is deteriorated.
[0166] Example 24 In this embodiment, the oxide solid electrolyte was changed from LATP to porous spherical LLTO (Li 0.5 La 0.5 The remaining parameters and conditions were the same as in Example 15, except for changing the catalyst to TiO3. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0167] [Table 13]
[0168] As can be seen from Table 13, compared with Example 15, the solid electrolyte is changed from LATP to LLTO, and there is no obvious change in the electrochemical and safety performance of the battery, because the performances of the two materials are almost the same.
[0169] Example 25 In comparison with Example 15, in this example, the oxide solid electrolyte was changed from LATP to porous spherical LZGO (Li 14 ZnGeO 16 ), the remaining parameters and conditions were the same as in Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0170] [Table 14]
[0171] As can be seen from Table 14, compared with Example 15, the oxide solid electrolyte LATP is changed to LZGO, the type of solid electrolyte is changed, the energy density of the battery is obviously reduced, the 3C rate discharge performance is deteriorated, and the safety performance of the battery is also obviously deteriorated. This is because the high ionic conductivity of LZTO increases the impedance of the positive plate, which leads to the deterioration of battery performance.
[0172] Example 26 In this example, the oxide solid electrolyte was changed from LATP to porous spherical LLZO (Li7La3Zr2O 12 ), the remaining parameters and conditions were the same as in Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0173] [Table 15]
[0174] As is clear from Table 15, compared with Example 15, the oxide solid electrolyte LATP is changed to LLZO, the type of solid electrolyte is changed, the energy density of the battery is reduced, the 3C rate discharge performance is deteriorated, and the ionic conductivity of LLZO is reduced compared with LATP, resulting in deterioration of the battery performance.
[0175] Example 27 Compared with Example 15, in this example, the porosity of the porous spherical oxide solid electrolyte was changed to 40%, and the rest of the parameters and conditions were the same as those in Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0176] [Table 16]
[0177] As is clear from Table 16, compared with Example 15, the porosity of the oxide solid electrolyte LATP changes from 50% to 40%, but there is almost no change in the energy density and rate performance of the battery.
[0178] Example 28 Compared with Example 15, in this example, the porosity of the porous spherical oxide solid electrolyte was changed to 5%, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0179] [Table 17]
[0180] As is clear from Table 17, compared with Example 15, the porosity of the oxide solid electrolyte LATP changes from 50% to 5%, and the porosity becomes smaller and the active sites for the reaction become fewer. As a result, the energy density and rate performance of the battery decrease. In addition, because the porosity becomes smaller, the absorption capacity for the heat generated in the positive electrode decreases, and therefore the safety performance also decreases.
[0181] Example 29 Compared with Example 15, in this example, the mass ratio of the positive electrode active material to the oxide solid electrolyte was 99.99:0.01, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0182] [Table 18]
[0183] As can be seen from Table 18, compared with Example 15, in this example, the content of solid electrolyte in the positive electrode material is reduced to 0.01%, and the remaining parameters remain unchanged. The energy density of the battery is obviously improved, and the rate performance is also improved, but the safety performance of the battery is not satisfactory. This is because the content of oxide solid electrolyte is reduced, so it cannot effectively barrier the contact between the ternary active particles, and it cannot absorb the heat generated in the positive electrode, resulting in the deterioration of the safety performance of the battery.
[0184] Example 30 Compared with Example 15, in this example, the mass ratio of the positive electrode active material to the oxide solid electrolyte was 85:15, except that the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0185] [Table 19]
[0186] As can be seen from Table 19, compared with Example 15, in this example, the content of the solid electrolyte in the positive electrode material is increased to 15%, and the energy density of the battery is obviously reduced, and both the cycle number and rate performance are obviously deteriorated. This is because the proportion of the positive electrode active material is reduced due to the high content of the solid electrolyte, and as a result, the electrochemical performance of the battery is deteriorated.
[0187] Example 31 Compared with Example 15, in this example, the particle size of the oxide solid electrolyte was 0.1 μm, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0188] [Table 20]
[0189] As is clear from Table 20, compared with Example 15, in this Example, the particle size of the oxide solid electrolyte changed from 0.8 μm to 0.1 μm, the particle size of the solid electrolyte became smaller, and a decrease in the energy density and rate performance of the battery was observed, but the safety performance of the battery was almost unchanged.
[0190] Example 32 Compared with Example 15, in this example, the particle size of the oxide solid electrolyte was 0.01 μm, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0191] [Table 21]
[0192] As is clear from Table 21, compared with Example 15, in this Example, the particle size of the oxide solid electrolyte changes from 0.8 μm to 0.01 μm, the particle size of the solid electrolyte becomes smaller, and a decrease in the energy density and rate performance of the battery is observed. The safety performance of the battery is also obviously deteriorated, mainly because the particles become smaller and are more likely to aggregate, resulting in a deterioration in the electrochemical performance and safety performance of the battery.
[0193] Example 33 Compared with Example 15, in this example, the particle size of the oxide solid electrolyte was 11 μm, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0194] [Table 22]
[0195] As can be seen from Table 22, compared with Example 15, the particle size of oxide solid electrolyte changes from 0.8 μm to 11 μm, the particle size of oxide solid electrolyte is obviously increased, the energy density of the battery is obviously deteriorated, the cycle performance is also deteriorated, and the rate performance of the battery is also obviously deteriorated. This is because the particle size of solid electrolyte increases, and the electrical resistance of material increases, resulting in deterioration of battery performance; furthermore, the safety performance of the battery is obviously deteriorated. This is because the particle size of oxide solid electrolyte increases, and the barrier effect against the contact between positive electrode particles becomes insufficient, so that the contact between ternary active particles cannot be effectively blocked, which adversely affects the safety performance of the battery.
[0196] Example 34 Compared with Example 15, in this example, the particle size of the oxide solid electrolyte was 10 μm, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0197] [Table 23]
[0198] As can be seen from Table 23, compared with Example 15, the particle size of the oxide solid electrolyte changes from 0.8 μm to 10 μm, the particle size increases, and the energy density and rate performance of the battery deteriorate, but it passes the safety performance test.
[0199] Example 35 Compared with Example 15, in this example, the porosity of the porous spherical oxide solid electrolyte was changed to 3%, and the rest of the parameters and conditions were the same as those in Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0200] [Table 24]
[0201] As can be seen from Table 24, compared with Example 15, the porosity of the oxide solid electrolyte LATP changes from 50% to 3%, the porosity is smaller, and the active sites of the reaction are obviously reduced. As a result, the energy density of the battery is reduced, the rate performance of the battery is reduced, and the porosity is reduced, so the absorption ability of the heat generated in the positive electrode is deteriorated, the transport performance of lithium ions is deteriorated, and the energy density is reduced.
[0202] Example 36 Compared with Example 15, in this example, the porosity of the porous spherical oxide solid electrolyte was changed to 70%, and the rest of the parameters and conditions were the same as those in Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0203] [Table 25]
[0204] As is clear from Table 25, compared with Example 15, the porosity of the oxide solid electrolyte LATP changes from 50% to 70%, the porosity increases, and the number of active sites for reaction obviously increases. As a result, the energy density and rate performance of the battery also increase. In addition, because the porosity increases, the absorption ability for heat generated in the positive electrode becomes stronger, and the transport performance of lithium ions becomes better, which results in improved safety performance.
[0205] Example 37 Compared with Example 15, in this example, the porosity of the porous spherical oxide solid electrolyte was changed to 80%, and the rest of the parameters and conditions were the same as those in Example 15. The lithium battery obtained in this example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0206] [Table 26]
[0207] As can be seen from Table 26, compared with Example 15, the porosity of oxide solid electrolyte LATP changes from 50% to 80%, the porosity increases, and the active sites of reaction are obviously increased. As a result, the energy density of the battery and the rate performance of the battery are also improved. In addition, because the porosity increases, the absorption ability of the heat generated in the positive electrode is strong, and the transport performance of lithium ions is good. As a result, the safety performance is also improved. However, when forming holes, the manufacturing process of the material is difficult, and if the porosity of the material is too large, the yield of the material will drop sharply.
[0208] Comparative Example 3 Compared with Example 15, in this comparative example, no oxide solid electrolyte was added to the ternary positive plate, and the rest of the parameters and conditions were the same as those of Example 15. The lithium battery obtained in this comparative example was subjected to electrical performance and safety performance tests, and the test results are shown below.
[0209] [Table 27]
[0210] As is clear from Table 27, in this comparative example, no solid electrolyte was added, and the energy density of the battery was improved, and the rate performance was also improved. However, the battery safety performance did not pass any of the needle punch, 180°C hot box, and approximately 50% deformation pressing tests. This is because the absence of an oxide solid electrolyte makes it impossible to form a barrier to prevent contact between the ternary active particles, and it is also impossible to absorb the heat generated in the positive electrode, resulting in a deterioration in the safety performance of the battery.
[0211] As can be seen from the comparison of Examples 15 to 37 and Comparative Examples 2 to 3, in the present invention, an oxide solid electrolyte is added to the ternary positive plate, and the safety of the lithium battery obtained using this positive plate is significantly improved. All of the lithium batteries in the examples passed the needle punch test, the test of heating at 180°C for 2 hours, and the 50% deformation pressing test, and the obtained lithium batteries have a high specific capacity of 300Wh / Kg or more.
[0212] As can be seen from the comparison between Comparative Example 2 and Example 15, a porous spherical oxide solid electrolyte is used in the present invention, and the lithium battery obtained using this oxide solid electrolyte has a higher capacity and better cycle performance.
[0213] As can be seen from the comparison of Examples 15, 17, and 24 to 26, the oxide solid electrolyte is preferably LATP or LLTO.
[0214] As can be seen from the comparison of Examples 15, 16, 22, 23, 29, and 30, the total mass of the positive electrode active material and the oxide solid electrolyte is 100%, and the content of the oxide solid electrolyte is 0.1-10 mass%, preferably 1-5 mass%. If the content of the solid electrolyte is too high, the content of the positive electrode active material will be reduced, which will have a negative impact on the energy density and electrochemical performance of the battery. If the content of the solid electrolyte is too low, the safety performance of the battery will not pass.
[0215] As can be seen from the comparison of Examples 15, 19-21, and 31-34, the particle size of the oxide solid electrolyte is 0.1-10 μm, preferably 0.5-3 μm. When the particle size of the oxide solid electrolyte is <0.1 μm, the particle size of the oxide solid electrolyte is too small, the interface resistance increases, ion transport is blocked, the interface impedance increases, and the energy density of the battery decreases. When the particle size of the oxide solid electrolyte is >10 μm, the particle size is too large, and the barrier effect against contact between positive electrode particles is insufficient. As a result, the improvement in safety is insufficient.
[0216] As can be seen from the comparison of Examples 15, 27, and 35 to 37, the porosity of the oxide solid electrolyte porous spherical particles is 5 to 70%, preferably 40 to 70%. If the porosity is too small, the active sites of the solid electrolyte are too few, the interface resistance is too large, and lithium ion transport is blocked, whereas if the porosity is too large, the difficulty of pore formation increases significantly, and the material yield decreases.
[0217] 1. Manufacturing of ternary electrode plates containing oxide solid electrolyte The ternary positive electrode active material, oxide solid electrolyte, conductive agent, and binder are weighed according to the proportion data listed in C1-C22, C25-C30 in Table 28. First, the ternary positive electrode active material and the oxide solid electrolyte are vacuum premixed to obtain a uniformly dispersed premixed material. The PVDF NMP binder solution is gradually added to the above uniformly dispersed premixed material, and then the conductive agent Super-P and CNT are gradually added and mixed uniformly to obtain a ternary positive electrode slurry with a certain fluidity. Then, the slurry is painted on an aluminum foil, blast dried, and roll pressed to obtain a positive electrode plate, which are respectively named C1, C2...C22, C25~C30. The conductive agent was carbon nanotubes and conductive carbon black (CNT+Super-P, the mass ratio of carbon nanotubes to conductive carbon black was 1:2), and the binder was polyvinylidene fluoride (PVDF). FIG. 5 shows a schematic diagram of the internal structure of the positive electrode material layer in a ternary electrode plate containing an oxide solid electrolyte.
[0218] 2. Manufacturing of ternary electrode plates without oxide solid electrolyte The ternary positive electrode active material, conductive agent, and binder are weighed according to the proportion data shown in C23 and C24 in Table 28. The PVDF NMP binder solution is gradually added to the ternary positive electrode active material, and mixed uniformly. Then, the conductive agent Super-P and CNT (the mass ratio of CNT and conductive carbon black Super-P is 1:2) are gradually added and mixed uniformly to obtain a ternary positive electrode slurry with a certain fluidity. Then, the slurry is painted on an aluminum foil, blast-dried, and roll-pressed to obtain a positive electrode plate, which is named C23 and C24, respectively. The types of conductive agent and binder were the same as in Example 38, and the remaining procedures were the same as in Example 38, except that the vacuum premixing step was omitted.
[0219] [Table 28]
[0220] The oxide solid electrolyte is Li 1.4 Al 0.4Ti 1.6 (PO4)3 (abbreviation LATP-1), Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (abbreviation LATP-2), Li 1.5 Al 0.5 Ti 1.5 (PO4)3 (abbreviation LATP-3), Li 6.4 La3Zr 1.6 Ta 0.6 O 12 (abbreviation LLZO-1), Li7La3Zr2O 12 (abbreviation LLZO-2), Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (abbreviation LAGP-1), Li 1.3 Al 0.3 Ge 1.7 (PO4)3 (abbreviation LAGP-2), Li 0.5 La 0.5 Ti O3 (abbreviation LLTO-1), Li 0.34 La 0.56 TiO3 (abbreviation LLTO-2), Li3OCl (abbreviation LOC), Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Zr 1 / 4 O3 (abbreviation LSTZ), Li 14 ZnGeO 16 (abbreviation LZGO). The ternary positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviation Ni80), LiNi 0.83 Co 0.12 Mn 0.05 O2 (abbreviation Ni83), LiNi 0.88 Co 0.09 Mn 0.03 O2 (abbreviation Ni88), LiNi 0.8 Co 0.15 Al 0.05 O2 (abbreviation NCA).
[0221] 3. Manufacturing of negative electrodes In the present invention, the negative electrode is generally graphite, silicon carbon, silicon oxycarbon, soft / hard carbon, mesocarbon microspheres, or composite metal lithium. In the present invention, there is no limitation on the negative electrode, as long as the surface capacity is matched with the positive electrode when manufacturing the battery core. More specifically, the negative electrode main active material, conductive agent, and binder were added to deionized water in a mass ratio of 96:2:2, mixed, and stirred uniformly to obtain a negative electrode slurry with a certain fluidity, which was then painted on copper foil, blast-dried, and roll-pressed to obtain negative electrode plates, designated A1, A2, ..., A5, respectively. Here, the conductive agent was a mixture of carbon nanotubes CNT and conductive carbon black Super-P in a mass ratio of 1:2, and the binder was a mixture of CMC and SBR in a mass ratio of 1:1.
[0222] [Table 29]
[0223] The silicon carbon material used was SL450A-SOC nano silicon carbon anode material manufactured by Liyang Tianmu Lead Battery Materials Technology Co., Ltd., and the silicon oxycarbon material used was S450~2A silicon oxycarbon anode material manufactured by Betelry New Energy Materials Co., Ltd.
[0224] 4. Battery core manufacturing A 15Ah soft pack battery core was manufactured according to the data in Table 30. Plate size: positive electrode 107mm*83mm, negative electrode 109mm*85mm.
[0225] [Table 30]
[0226] Among these, Examples 38 to 57 and 60 to 65 are liquid lithium batteries, in which a double-sided ceramic separator is used as the separator, and a commercially available general electrolyte is used as the electrolyte. In Comparative Examples 4 to 7 and Examples 38 to 57, the composition of the electrolyte is 1 mol / L LiPF6-EC / DEC (3:7, V / V) + 2 wt% VC + 1 wt% LiDFOB, and in Example 6 In Examples 0 to 62, the composition of the electrolyte was 1.2 mol / L LiPF6-EC / EMC (3:7, V / V) + 2 wt% FEC + 1 wt% LiDFOB, in Examples 63 to 65, the composition of the electrolyte was 1.2 mol / L LiPF6-EC / DEC (3:7, V / V) + 2 wt% FEC + 1 wt% LiDFOB + 1 wt% 1,3-PS, and in Examples 58 to 59, a semi-solid lithium battery was used, a PVDF-HFP-based gel polymer electrolyte membrane was used, and the composition of the electrolyte was 1 mol / L LiPF6-EC / DEC (3:7, V / V) + 2 wt% VC + 1 wt% LiDFOB.
[0227] 5. Battery performance test The lithium batteries produced in Examples 38 to 65 and Comparative Examples 4 to 7 were tested for electrical resistance, capacity retention rate after 100 cycles, and capacity retention rate after 1000 cycles, and the results are shown in Table 31. Test voltage range: 2.75 to 4.2 V, charge / discharge current: 1 C / 1 C.
[0228] [Table 31]
[0229] In the present invention, the oxide solid electrolyte is blended into the high nickel ternary positive plate to improve the safety of the battery. As is clear from the comparison of Comparative Examples 4-5 and Examples 37-65, the performance of the battery manufactured by the present invention is not significantly affected. This is mainly because the oxide solid electrolyte particles themselves have a certain ion conductive ability, so when the oxide solid electrolyte is introduced within the range of the solid electrolyte content described in the present invention, it does not obviously inhibit the ion transport ability in the positive electrode, and the endothermic effect of the oxide solid electrolyte reduces the average temperature of the positive electrode active material during charging and discharging, and reduces the side reaction of the ternary positive electrode active material at high temperatures, which is advantageous in ensuring a long cycle life of the battery. However, the blended oxide solid electrolyte If the particle size of the electrolyte is too small or the amount of the electrolyte blended is too large, the internal resistance of the battery increases and the energy density of the battery decreases.
[0230] 6. Safety test of battery core by needle punching The lithium batteries manufactured in Examples 37 to 65 and Comparative Examples 4 to 7 were subjected to safety tests using needle punching in accordance with the safety requirements and test methods for lithium ion batteries GB / T31485-2015 power batteries for electric vehicles. Needle punch test The battery was charged at a constant current and constant voltage of 1C with a cut-off current of 0.05C. A high-temperature resistant steel needle of φ5mm was pierced at a speed of 25±5mm / s in a direction perpendicular to the battery plate, preferably near the geometric center of the surface to be pierced. The steel needle was retained in the battery and observed for 30 minutes. Changes in the surface temperature of the battery core during this process were monitored, and the presence or absence of fire or explosion of the battery core was recorded. The results are shown in Table 32.
[0231] [Table 32]
[0232] In the present invention, the oxide solid electrolyte is blended into the high nickel ternary positive plate to improve the safety of the battery. As is clear from the comparison of Comparative Examples 4-5 and Examples 38-42, 44-48, 50-51, and 53-65, the batteries manufactured according to the present invention did not ignite or explode during needle punching, and the surface temperature of the battery core during needle punching was 41.3-57.6°C, improving the safety of the battery. On the other hand, in Comparative Examples 4-5 in which the oxide solid electrolyte was not added to the positive plate, the batteries manufactured using these positive plates ignited or exploded during needle punching, thermal runaway occurred, and the surface temperature of the battery core reached a maximum of 793.7°C. Mainly, the oxide solid electrolyte is added to the ternary positive active material to effectively prevent contact between the ternary active particles, improving the thermal stability of the material, and the present invention This is because the oxide solid electrolyte itself has a certain heat capacity and can absorb part of the heat generated in the positive electrode, thereby mitigating overheating of the positive electrode. As is clear from Comparative Examples 6-7 and Examples 38-42, in Comparative Examples 6-7, an oxide solid electrolyte was added, but if the particle size of the oxide solid electrolyte is too small, ion transport is blocked, the interface impedance increases, and the energy density of the battery decreases, and if the particle size of the oxide solid electrolyte is too large, the barrier effect against contact between the positive electrode particles is insufficient, and as a result, the improvement in safety is insufficient, and the needle punch test is not passed. From this, it can be seen that if the particle size mixed in the positive electrode is too small or too large, the effect of improving safety while ensuring the energy density of the battery cannot be obtained. As can be seen from Examples 40, 43 to 48, in Example 43, an oxide solid electrolyte was added to the positive electrode plate, but the amount of the oxide solid electrolyte was too small, so the heat absorption and heat insulation effects of the solid electrolyte were insufficient, the safety improvement was insufficient, and the needle punch test could not be passed, while in Example 48, in which an oxide solid electrolyte was added to the positive electrode plate, the needle punch test was passed, but the amount was too large, and the energy density of the battery was reduced. From this, it can be seen that the effect of improving safety while ensuring the energy density of the battery cannot be obtained even if the amount of the oxide solid electrolyte in the positive electrode is too small or too large. In Example 49, oxide solid electrolyte is added, and its particle size D50 is in the preferred range of 0.1-3 μm, and its amount is in the preferred range of 0.1-10%, but the ratio of ternary positive electrode material D50 to oxide solid electrolyte D50 is less than 5, that is, the particle sizes of both are close, so in this particle size and content range, the amount of oxide solid electrolyte is insufficient to barrier the contact between the ternary positive electrode active material particles, resulting in poor safety and failure to pass the needle punch test; however, the surface temperature is lower than that of the battery core of Comparative Example 4-5, which shows that the oxide solid electrolyte can reduce the energy during thermal runaway to a certain extent. In Example 52, oxide solid electrolyte is added, and its particle size D50 is in the preferred range of 0.1-3 μm, and its amount is in the preferred range of 0.1-10%. However, the ratio of ternary positive electrode material D50 to oxide solid electrolyte D50 is greater than 5, but the rotation speed of premixing is too small, so the dispersion effect is poor and the particles are prone to agglomeration. As a result, the safety is poor and the needle punch test cannot be passed. However, the surface temperature is lower than that of the battery cores of Comparative Examples 4-5, which shows that the oxide solid electrolyte can reduce the energy during thermal runaway to a certain extent. As is clear from Examples 40, 55 to 57, and 60 to 65, regardless of which oxide solid electrolyte is doped, the safety performance of the battery is improved, although to different degrees. Among these, the effect of improving safety performance by LATP is most suitable. As is clear from Examples 40, 61 to 62, Examples 53, 64, Examples 54, 63, and Examples 56 and 65, the electrolyte components have little effect on battery safety for each electrolyte, and in any case, the battery can pass the needle punch test without any problems. As is clear from Examples 60 to 65, when the positive electrode plate provided by the present invention is used in combination with a common commercially available electrolyte, it has the effect of improving the safety of the battery core, and the battery core can pass the needle punch test without any problems.
[0233] 7. Battery core safety test in 180℃ hot box The battery was charged at a constant current and constant voltage of 1C, with a cut-off current of 0.05C, and heated to 180℃ for 2 hours. The battery was heated to 180℃ at a temperature rise rate of 5℃ / mm and kept at that temperature for 2 hours. After observing for 1 hour, those that did not ignite or explode were rated as passing, and those that did not were rated as failing. The changes in the surface temperature of the battery core during this process were monitored, and the test results are shown in Table 33.
[0234] [Table 33]
[0235] In the present invention, the oxide solid electrolyte is blended with the high-nickel ternary positive electrode plate, thereby improving the safety of the battery. As is clear from Comparative Examples 4 to 5 and Examples 38 to 42, 44 to 47, 50 to 51, and 53 to 65, the batteries manufactured by the present invention have a high degree of thermal stability in a 180°C hot box test. In the test, the surface temperature of the battery core was 181.4-188.7°C, the weight loss rate of the battery was 15.1%-27.1%, and there was no fire or explosion. On the other hand, for Comparative Examples 4-5, in which the oxide solid electrolyte was not added to the positive electrode plate, the battery manufactured using this experienced thermal runaway, and the surface temperature of the battery reached a maximum of 560.8°C. This is mainly because the oxide solid electrolyte is added to the ternary positive electrode active material to effectively barrier the contact between the ternary active particles and improve the thermal stability of the material, and secondly, the oxide solid electrolyte of the present invention itself has a certain heat capacity, so that it can absorb part of the heat generated in the positive electrode and mitigate overheating of the positive electrode. For this reason, the battery passes the 180°C hot box test without any problems.
[0236] As is clear from Comparative Examples 6-7 and Examples 38-42, in Comparative Examples 6-7, an oxide solid electrolyte was added, but if the particle size of the oxide solid electrolyte is too small, ion transport is blocked, the interface impedance increases, and the energy density of the battery decreases, and if the particle size of the oxide solid electrolyte is too large, the barrier effect against contact between the positive electrode particles is insufficient, and as a result, the improvement in safety is insufficient, and the battery does not pass the 180°C hot box test. This shows that if the particle size of the positive electrode compound is too small or too large, the effect of improving safety while ensuring the energy density of the battery cannot be obtained.
[0237] As can be seen from Examples 40 and 43 to 48, in Example 43, an oxide solid electrolyte was added to the positive electrode plate, but if the amount of the oxide solid electrolyte added to the positive electrode was too small or too large, the desired safety improvement effect could not be obtained, and if the amount of the oxide solid electrolyte added was too small, the heat absorption and heat insulation effects of the solid electrolyte were insufficient, and the improvement in safety was insufficient. In Example 48, in which an oxide solid electrolyte was added to the positive electrode plate, the battery passed the 180°C hot box test, but the amount added was too large, resulting in a decrease in the energy density of the battery.
[0238] In Example 49, oxide solid electrolyte is added, and its particle size D50 is in the preferred range of 0.1-3 μm, and its amount is in the preferred range of 0.1-10%, but the ratio of ternary positive electrode material D50 to oxide solid electrolyte D50 is less than 5, that is, the particle sizes of both are close, so in this particle size and content range, the amount of oxide solid electrolyte is insufficient to barrier the contact between the ternary positive electrode active material particles, resulting in poor safety and failure to pass the 180°C hot box test, but the surface temperature is lower than that of the battery core of Comparative Examples 4-5, which shows that the oxide solid electrolyte can reduce the energy during thermal runaway to a certain extent.
[0239] In Example 52, an oxide solid electrolyte is added, and its particle size D50 is in the preferred range of 0.1-3 μm, and its amount is in the preferred range of 0.1-10%, and the ratio of the ternary positive electrode material D50 to the oxide solid electrolyte D50 is greater than 5, but the rotation speed of the premix is too small, so the dispersion effect is poor and the particles are prone to agglomeration, resulting in poor safety and failure to pass the 180°C hot box test. However, the surface temperature is lower than that of the battery cores of Comparative Examples 4-5, which indicates that the oxide solid electrolyte can reduce the energy during thermal runaway to a certain extent.
[0240] In the embodiment provided in the present invention, the ternary positive electrode material used is LiNi x Co y M 1-x-y In O2, the nickel content x is 0.80, 0.83 or 0.88. The higher the nickel content of the high-nickel ternary positive electrode material, the worse the thermal stability. As can be seen from Examples 54 and 55, even when the positive electrode plate provided by the present invention has a high nickel content (x=0.88), the battery core can pass the hot box test without any problems. Even when the positive electrode active material has a low Ni content (x=0.6-0.8), the positive electrode plate provided by the present invention can maintain good safety.
[0241] As is clear from Examples 40, 55 to 57, and 60 to 65, which oxide solid electrolyte is Even when the electrolyte is mixed with the electrolyte, the safety performance of the battery is improved to different degrees, and among these, the effect of improving the safety performance by LATP is the most suitable. As is clear from Examples 40, 61 to 62, Examples 53, 64, Examples 54, 63, and Examples 56, 65, the influence of the electrolyte components on the battery safety is small for each electrolyte.
[0242] As is clear from Examples 60 to 65, when the positive electrode plate provided by the present invention is used in combination with a common commercially available electrolyte, it has the effect of improving the safety of the battery core, and the battery core can pass the hot box test without any problems.
[0243] It should be noted that the above is merely a preferred embodiment of the present invention, and a person skilled in the art may make some improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should be considered as within the scope of the present invention.
Claims
1. A positive electrode plate for a lithium battery, comprising at least one lithium-rich compound selected from a lithium-rich manganese-based solid solution, a lithium-rich solid electrolyte, and lithium-free silicon monoxide.
2. The lithium-rich compound is capable of releasing lithium ions under extreme conditions in a battery; Preferably, the battery extreme conditions include at least one of battery overcharging, high temperature, needle punching, pressing, internal short circuit, external short circuit, thermal abuse, and overheating; Preferably, the molecular formula of the lithium-rich manganese-based solid solution is xLi 2 MnO 3 ・(1-x)LiMO 2 2. The positive electrode plate for a lithium battery according to claim 1, characterized in that: (wherein x is 0<x≦1, and M is at least one selected from Ni, Co and Mn).
3. The lithium-rich solid electrolyte is Li 7 La 3 Zr 2 O 12 and Li 7 La 3 Zr 2 O 12 3. The positive electrode plate for a lithium battery according to claim 1, characterized in that the doping element is selected from materials doped with other elements, and the doping element is at least one of La, Nb, Sb, Ga, Te, W, Al, Sn, Ca, Ti, Hf, and Ta.
4. The molecular formula of the lithium-free silicon monoxide is Li x SiO y (wherein x is 1.4 to 2.1, and y is 0.9 to 1.1).
5. The positive electrode plate for a lithium battery according to any one of claims 1 to 4, characterized in that the particle diameter D50 of the lithium-rich compound particles is 0.1 to 10 µm, preferably 0.5 to 2 µm.
6. The total mass of the positive electrode active material and the lithium-rich compound in the positive electrode plate for lithium batteries is 100%, and the content of the lithium-rich compound is 0.1 to 20 mass%, preferably 1 to 5 mass%. The positive electrode plate for lithium batteries according to any one of claims 1 to 5, characterized in that
7. The surface capacity of the positive electrode plate for the lithium battery is 4 mAh / cm 2 That's all. Preferably, the positive electrode active material in the positive electrode plate for lithium batteries is LiNi x Co 1-x-y M y O 2 (wherein, x≧0.8, y≦0.2, and M is any one or a combination of at least two selected from Mn, Al, and Mg). The positive electrode plate for a lithium battery according to any one of claims 1 to 6.
8. A step of premixing a positive electrode active material and a lithium-rich compound to obtain a premixed powder; mixing the premixed powder, a binder liquid, and a conductive agent to obtain a positive electrode slurry; and applying the positive electrode slurry onto a current collector, baking, cold pressing, and forming into a sheet to obtain the positive electrode plate for a lithium battery. Preferably, the method for manufacturing a positive electrode plate for a lithium battery according to any one of claims 1 to 7, characterized in that the pre-mixed powder, the binder liquid, and the conductive agent are mixed by adding the binder liquid to the pre-mixed powder, and then adding the conductive agent to obtain the positive electrode slurry.
9. The positive electrode plate for a lithium battery according to any one of claims 1 to 7 is included, Preferably, the battery further includes a negative electrode plate, and the negative electrode active material in the negative electrode plate is selected from silicon monoxide and / or silicon carbon; Preferably, the negative electrode plate includes a negative electrode active material, a conductive agent, a thickener, and a binder, Preferably, the battery further comprises a separator.
10. The separator is selected from separators coated with a ceramic coating; The battery according to claim 9, wherein the separator preferably has a thickness of 10 to 40 μm and a porosity of 20 to 60%.
11. A ternary positive electrode plate for a lithium battery having high safety and high capacity, comprising a current collector and a positive electrode active material layer located on a surface of the current collector, The positive electrode active material layer includes an oxide solid electrolyte capable of transporting lithium ions, the oxide solid electrolyte being in the form of porous spherical particles.
12. A ternary positive plate according to claim 11, characterized in that the porosity of said porous spherical particles is 5-70%, preferably 40-70%.
13. The ternary positive electrode plate according to claim 11 or 12, characterized in that the particle size of the oxide solid electrolyte is 0.1 to 10 μm, preferably 0.5 to 3 μm.
14. The ternary positive electrode plate according to any one of claims 11 to 13, characterized in that the content of the oxide solid electrolyte is 0.1 to 10 mass%, preferably 1 to 5 mass%, with the total mass of the cathode active material and the oxide solid electrolyte in the cathode active material layer being 100%.
15. The oxide solid electrolyte includes at least one of a NASICON structure, a perovskite structure, an anti-perovskite structure, a LISICON structure, and a garnet structure; Preferably, the NASICON structure is Li 1+x A x Ge 2-x (P.O. 4 ) 3 , Li 1+x A x Ge 2-x (P.O. 4 ) 3 The same crystalline heteroatom doped compound of Li 1+y A y Ti 2-y (P.O. 4 ) 3 and Li 1+y A y Ti 2-y (P.O. 4 ) 3 At least one selected from the heteroatom-doped compounds of the above formula (1), Preferably, the perovskite structure is Li 3z La 2/3-z TiO 3 , Li 3z La 2/3-z TiO 3 The same crystalline heteroatom doped compound of Li 3/8 Sr 7/16 T 3/4 Hf 1/4 O 3 , Li 3/8 Sr 7/16 T 3/4 Hf 1/4 O 3 The same crystalline heteroatom doped compound of Li 2a-b Sr 1-a T b Zr 1-b O 3 and Li 2a-b Sr 1-a T b Zr 1-b O 3 At least one of the heteroatom-doped compounds of the above formula (1) is selected from the group consisting of the above-mentioned compounds, Preferably, the antiperovskite structure is Li 3-2x M x HalO, Li 3-2x M x The homocrystalline heteroatom doped compound of HalO, Li 3 OCl and Li 3 At least one selected from the group consisting of heteroatom-doped compounds of the same crystal form as OCl, wherein Hal contains Cl and / or I, and M is Mg. 2+ , Ca 2+ , Sr 2+ Or Ba 2+ Any one or a combination of at least two selected from Preferably, the LISICON structure is Li 4-c S 1-c P c O 4 , Li 4-c S 1-c P c O 4 The same crystalline heteroatom doped compound of Li 14 ZnGe 4 O 16 and Li 14 ZnGe 4 O 16 At least one selected from the heteroatom-doped compounds of the above formula (1), Preferably, the garnet structure is Li 7-d La 3 Zr 2-d O 12 And / or Li 7-d La 3 Zr 2-d O 12 The ternary positive electrode plate according to any one of claims 11 to 14, characterized in that the heteroatom doping compounds are selected from the same crystalline forms of the compounds:
16. The surface capacity of the ternary positive plate is 4 mAh / cm 2 The ternary positive electrode plate according to any one of claims 11 to 15, characterized in that
17. the positive electrode active material in the positive electrode active material layer is selected from high nickel ternary materials; Preferably, the high nickel ternary material comprises lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminate; Preferably, the molecular formula of the lithium nickel cobalt manganese oxide is LiNi x Co y Mn 1-x-y O 2 The molecular formula of the lithium nickel cobalt aluminate is LiNi x Co y A 1-x-y O 2 17. The ternary positive plate of any one of claims 11 to 16, wherein x≧0.
6.
18. A step of premixing a positive electrode active material and an oxide solid electrolyte to obtain a premixed powder; adding a binder liquid and a conductive agent to the premixed powder and mixing them to obtain a positive electrode slurry; and applying the positive electrode slurry onto a current collector and drying the positive electrode slurry to obtain the ternary positive electrode plate.
19. A lithium battery comprising the ternary positive electrode plate according to any one of claims 11 to 17.
20. The lithium battery includes any one of a liquid lithium battery, a semi-solid lithium battery, and a solid-state lithium battery; Preferably, the liquid lithium battery comprises a ternary positive plate, a negative plate and a liquid electrolyte according to any one of claims 11 to 17, Preferably, the semi-solid lithium battery comprises the ternary positive electrode plate, the negative electrode plate and an electrolyte layer according to any one of claims 11 to 17, and the electrolyte layer contains a liquid electrolyte material; Preferably, the solid-state lithium battery comprises a ternary positive electrode plate, a negative electrode plate and a solid electrolyte layer according to any one of claims 11 to 17, 20. The lithium battery according to claim 19, wherein the solid electrolyte in the solid electrolyte layer is at least one selected from the group consisting of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.
21. a current collector; and a positive electrode material layer located on a surface of the current collector, the positive electrode material layer including ternary positive electrode active material particles, a conductive agent, a binder, and oxide solid electrolyte particles capable of conducting lithium ions; The surface capacity of the positive electrode plate is 4 mAh / cm 2 The above-mentioned ternary positive electrode plate for a lithium battery is characterized in that the particle diameter D50 of the oxide solid electrolyte particles is 0.1 to 3 μm.
22. The particle diameter D50 of the oxide solid electrolyte particles is 0.5 to 2 μm, Preferably, the content of the ternary positive electrode active material particles is 80 to 98% based on the total mass of the ternary positive electrode active material particles, the conductive agent, the binder and the oxide solid electrolyte particles being 100%; Preferably, the content of the oxide solid electrolyte is 0.1 to 10%, preferably 1 to 5%, based on the total mass of the ternary positive electrode active material particles, the conductive agent, the binder and the oxide solid electrolyte particles being 100%; Preferably, the content of the conductive agent is 0.1 to 8% based on the total mass of the ternary positive electrode active material particles, the conductive agent, the binder and the oxide solid electrolyte particles being 100%, Preferably, the total mass of the ternary positive electrode active material particles, the conductive agent, the binder and the oxide solid electrolyte particles is 100%, and the content of the binder is 0.1 to 10%.
23. The oxide solid electrolyte particles are Li 1+x1 A x1 Ge 2-x1 (P.O. 4 ) 3 or its isocrystalline heteroatom-doped compound, Li 1+x2 A x2 Ti 2-x2 (P.O. 4 ) 3 or its isocrystalline heteroatom-doped compound, Li with perovskite structure 3x3 La 2/3-x3 TiO 3 Or its homocrystalline heteroatom-doped compound Things, Li 3/8 Sr 7/16 T 3/4 Hf 1/4 O 3 or its isocrystalline heteroatom-doped compound, Li 2x4-y1 Sr 1-x4 T y1 Zr 1-y1 O 3 Or its isocrystalline heteroatom-doped compound, Li with antiperovskite structure 3-2x5 M x5 HalO, Li 3 OCl or its isocrystalline heteroatom doped compound, Li 4-x6 S 1-x6 P x6 O 4 or its isocrystalline heteroatom-doped compound, Li 14 ZnGe 4 O 16 or its isocrystalline heteroatom-doped compound, Li of garnet structure 7-x7 La 3 Zr 2-x7 O 12 or a combination of at least two of the heteroatom-doped compounds thereof, wherein 0<x1≦0.75, 0<x2≦0.5, 0.06≦x3≦0.14, 0.25≦y1≦1, x4=0.75y1, 0≦x5≦0.01, 0.5≦x6≦0.6; 0≦x7<1; and M is Mg. 2+ , Ca 2+ , Sr 2+ Or Ba 2+ wherein Hal is an element Cl or I, Preferably, the oxide solid electrolyte particles are Li 1+x2 A x2 Ti 2-x2 (P.O. 4 ) 3 And / or Li 7-x7 La 3 Zr 2-x7 O 12 and preferably Li 1+x2 A x2 Ti 2-x2 (P.O. 4 ) 3 The positive electrode plate according to claim 21 or 22,
24. the ternary positive electrode active material particles include lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminate; Preferably, the chemical composition of the ternary positive electrode active material particles is LiNi x Co y M 1-x-y O 2 (M is at least one of Mn and Al, and x≧0.6); Preferably, the conductive agent comprises any one or a combination of at least two of Super-P, KS-6, carbon black, carbon nanofiber, CNT, acetylene black, or graphene, and is preferably a combination of carbon nanotubes and Super-P; Preferably, the binder includes any one or a combination of at least two of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropene, polyethylene oxide, and polytetrafluoroethylene. The positive electrode plate according to any one of claims 21 to 23.
25. The positive electrode plate according to any one of claims 21 to 24, characterized in that the ratio of the particle diameter D50 of the ternary positive electrode active material particles to the particle diameter D50 of the oxide solid electrolyte particles is 5 or more.
26. Step S1 of premixing positive electrode active material particles including ternary positive electrode active material particles and oxide solid electrolyte particles to obtain a premixed material; Step S2 of adding a binder liquid to the premixed material and mixing to obtain a primary slurry; Step S3 of adding and mixing a conductive agent to the primary slurry to obtain a secondary slurry; The surface capacity of the plate is 4mAh / cm 2 The method for producing a positive electrode plate according to any one of claims 21 to 25, further comprising a step S4 of applying the secondary slurry onto a current collector, baking the slurry, and performing roll pressing to obtain a positive electrode plate.
27. The premixing is vacuum premixing or premixing performed under a dew point of ≦−30° C., Preferably, the premixing and mixing is carried out in a ball mill or a stirrer; Preferably, the premixing and mixing are carried out using a planetary centrifugal mixer, the revolution speed being 20 rpm or more, independently preferably 30 to 90 rpm, and the rotation speed being 200 rpm or more, independently preferably 500 to 2000 rpm; Preferably, the premixing time is between 0.5 and 4 h, preferably between 1 and 2 h; Preferably, the dew point is −45° C. or less, more preferably −60° C. or less.
27. The method according to claim 26.
28. The manufacturing process of the positive plate includes adding oxide solid electrolyte particles having a particle size D50 of 0.1 to 3 μm and dispersing them between the positive active material particles, and the surface capacity of the positive plate is 4 mAh / cm 2 The method for improving the safety of a lithium battery is as described above.
29. A lithium battery comprising the positive electrode plate according to any one of claims 21 to 25.
30. Including liquid lithium batteries or semi-solid lithium batteries, Preferably, the liquid lithium battery comprises the positive electrode plate, the negative electrode plate and a liquid electrolyte according to any one of claims 21 to 25, Preferably, the semi-solid lithium battery comprises a positive electrode plate according to any one of claims 21 to 25, a negative electrode plate, and an electrolyte layer containing a liquid electrolyte.
Citation Information
Patent Citations
Lithium secondary battery and its manufacturing method
JP2003059492A
Positive electrode for secondary battery, method for manufacturing positive electrode for secondary battery, and all-solid secondary battery
JP2014143133A
Nonaqueous secondary battery positive electrode material, nonaqueous secondary battery positive electrode, and nonaqueous secondary battery
JP2014175278A
Manufacturing method of all solid-state battery, manufacturing method of electrode, and manufacturing method of electronic device
JP2016189339A
Secondary battery containing solid electrolyte layer
JP2016502746A